Metabolomics-based analysis of dynamic metabolic trajectories and regulatory networks in two-stage fermentation of kiwifruit wine - Wangsheng Sun; Pengfei Bi; Wanju Yan; Rou Cai; Zhendong Zhang; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Jing Guo (Food Microbiology, 2027)

From inner-bay preservation to offshore dissipation: Spatiotemporal patterns and tracing of pharmaceuticals in Shenzhen Bay of the greater bay area, South China - Guangyang Cheng; Haoshuai Li; Lei Xing; Yang Zhou; Danxu Guo; Zimin Wang; Siqi Zhao; Zongshan Zhao; Shuhong Fang; Fang Chen; Rui Bao (Marine Pollution Bulletin, 2026)

Indole alkaloids from the roots of Nauclea officinalis and their chemotaxonomic significance - Shan-Ze Yin; Bao-Chan Liu; Guo-Lan Ma; Jiu-Wei Ma; Xi-Yang Lei; Bin-Bao Wang; Rui Li; Shao-Jie Lu; Wei-Min Gao; Pei-Gang Ouyang; Cai-Feng Ding (Biochemical Systematics and Ecology, 2026)

Cropping diversification increases microbial network complexity associated with enhanced soil multifunctionality and resistance to global change - Qian Guo; Peng He; Rui Li; Rong Yang; Jianing Wang; Tengfei Ma; Ning Ling; Lina Zheng; Zhaoming Wang (Soil and Tillage Research, 2026)

Construction of CdxZn1-xS for H2 production coupled with benzyl alcohol oxidation: Regulation of electrophilic and nucleophilic properties - Mengqi Guo; Qing Xi; Jilong Qin; Jianxin Liu; Yawen Wang; Yunfang Wang; Houfen Li; Fangxia Xie; Caimei Fan; Rui Li; Jiancheng Wang (Journal of Environmental Sciences, 2026)

Study on the O2 migration pathway and critical product formation mechanism in the water immersion coal oxidation - Guo-yu Shi; Xin-xiao Lu; Guan Wang; Zhao Yang; Long He; Rui-nan Zhang (Fuel, 2026)

Balancing fermentation control and aroma complexity in semi-spontaneous kiwifruit fermentation through Saccharomyces cerevisiae inoculum level - Wanju Yan; Yuanjing Li; Zitong Zhang; Rou Cai; Sinuo Feng; Jia Han; Wangsheng Sun; Rui Cai; Zhouli Wang; Jing Guo (Food Research International, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

Addressing the protein challenge in aquaculture: Nutritional attributes, application bottlenecks and refinement strategies for single-cell protein - Jiayv Zhang; Shanfei Fu; Rui Li; Mengxue Li; Zhenni Cheng; Xiaolei Fan; Rongbo Guo; Haiqing Wang (Animal Feed Science and Technology, 2026)

Investigation of electrode-free, room temperature, flexible NH3 sensors with high stability and sensitivity using MXene@PANI-MWCNTs ink - Jiahui Zheng; Bochao Ma; Xiaoqing Cui; Rui Wang; Li An; Bin Guo; Hongyan Zhang (Analytica Chimica Acta, 2026)

UPCRISPR: an ultrafast, one-tube multiplexed nucleic acid detection system for resolving the diagnostic gray zone in HPV16/18 detection - Linlin Bai; Dianwei Liu; Chunyan Qian; Weiqi Yuan; Kaiming Guo; Yao Wang; Feng Qian; Mingmin Shi; Bei Wang; Rui Wang (Analytica Chimica Acta, 2026)

Biochar strengthens rainfall regime resistance of soil inorganic C by enhancing pH–bicarbonate and carbonic anhydrase regulation in dryland region - Yuhao Wang; Yanbo Ji; Shutong Guo; Lin Sun; Enke Liu; Zhikuan Jia; Kadambot H.M. Siddique; Rui Qian; Ting Wei; Peng Zhang (Agriculture, Ecosystems & Environment, 2026)

A hybrid machine learning and data assimilation framework for penman–monteith evapotranspiration estimation over China - Xiaowen Wu; Xiang Li; Jianli Ding; Shaomin Liu; Tongren Xu; Lisheng Song; Sayed M. Bateni; Ziwei Xu; Dongxing Wu; Xinlei He; Jinjie Wang; Rui Liu; et al. (Remote Sensing of Environment, 2026)

Effect of double-cropping pattern on biological yield and quality of silage corn across different cropping systems in the Hebei region - Liang Song; Min Jia; Quanguo Zhang; Jianghao Wang; Liwei Wang; Rui Guo; Yuanyuan Yan; Jianfeng Wei; Xinghua Li; Wei Song (Next Research, 2026)

Nonradical pathway in peroxymonosulfate-based Fenton-like reactions triggered by the active Fe-Cu dual sites encapsulated in endogenous N-rich biochar - Rui Yang; Chaoting Jiang; Wangbo Wang; Xianshu Zhou; Fangshu Xie; Mingming Ta; Tuo Wang; Haifang Cai; Juan Guo; Weihuang Zhu (Journal of Environmental Chemical Engineering, 2026)

A review of molybdenum disulfide-based materials (MoS2) for piezocatalytic degradation of organic pollutants - Sa Li; Jiarui Zhang; Xuefei Lei; Biao Wang; Wei Cai; Xuanwen Liu; Rui Guo (Journal of Environmental Chemical Engineering, 2026)

From molecular assembly to biological function: an ovalbumin-fucoidan complex stabilized emulsion for enhancing the antioxidant efficacy of galangin - Yitong Wang; Rui Wang; Qiaoying Guo; Xiaoqian Xu; Hui Teng; Lei Chen; Yanan Zhao (Food Chemistry, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

Ultrasonic torsional wave excitation using a double-layer flexible magnetostrictive transducer for HDPE pipe monitoring - Kai Wang; Yizhou Guo; Yini Song; Yiru Xiao; Rui Zhang (Engineering Structures, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Reaction kinetics of typical inorganic salts in H2–Air explosion suppression and the synergistic regulation mechanism of multi-elements - Qiuhong Wang; Rui Guo; Zhenmin Luo; Hu Wen; Xianfeng Chen; Wenzhe Mao; Qingfeng Wang; Qiulin Li; Yifan Li (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Amplitude-controlled dynamic structural colors on wrinkling surfaces for facile multilevel strain-resolved optical encryption - Dengchong Feng; Shirui Wu; Yuxin Liu; Qi Guo; Rui Chen; Yu Chen; Yuzhao Yang; Haiqiang Wu; Zhiquan Zhao; Shaolin Lu; Zetong Ma; Cheng Wang; et al. (Chemical Engineering Journal, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

Spirofluorene-grafted triazine branched poly(aryl piperidinium) anion exchange membranes for high performance water electrolysis and flow batteries - Wei-Feng Yang; Yong-Xin An; Rui Guo; Han Yan; Tian-Tian Wang; Chang-Ping Liu; Yong-Mei Tian; Wen-Bin Sun (Chemical Engineering Journal, 2026)

Microbially induced hydroxyapatite improves simultaneous nitrogen and phosphorus removal in aerobic granular sludge - Fan Yang; Gonglei Wang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Jinsong Guo; Fang Fang (Bioresource Technology, 2026)

Buckling mode shifting of subsea pipelines under linear temperature field - Dongyang Liu; Qian Zhang; Zhenkui Wang; Shengjie Rui; Lizhong Wang; Zhen Guo (Ocean Engineering, 2026)

Paleoenvironmental response in the South China Sea from the Middle Miocene Climatic Optimum to Middle Miocene Climate Transition: Geochemical records from an isolated carbonate platform - Ning Guo; Wei Jiang; Tianlai Fan; Shendong Xu; Rui Wang; Jian-xin Zhao; Yue-xing Feng; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

A Porous Zn-Salen-Based Organic Ionic Polymer as a Robust Bifunctional Catalyst for CO2 Fixation via Epoxide Cycloaddition - Guo-Ling Li; Rui-Yao Qin; Meng-Meng Wang; Qing Li; Shijian Lu; Jin-Shui Su; Qi Zhang; Yun Zhao; Ran Zhang; Zhong-Hai Ni (Journal of Environmental Chemical Engineering, 2026)

Characterization of GSTz2 involved in cyantraniliprole and emamectin benzoate detoxification in Drosophila suzukii - Yongqi Yan; Chongzhi Wang; Mingzhe Li; Shiwei Guo; Xuxing Li; Jingyan Yu; Xiaoqing Fang; Rui Bi (Journal of Asia-Pacific Entomology, 2026)

Time-resolved structural remodeling and bioactivity changes of Lentinula edodes polysaccharides during fermentation by Limosilactobacillus fermentum CICC 21828 - Yue Liu; Saiqun Wang; Lu Liu; Zidan Zhao; Rui Cai; Jing Guo; Tianli Yue; Yahong Yuan; Zhouli Wang (Food Bioscience, 2026)

Copper-doped Coptidis Rhizoma-derived carbon dots (Cu-CR-CDs) nanozymes exhibit intestinal protective effects against Escherichia coli-induced diarrhea - Hongrui Guo; Rui Du; Zijing Dai; Zhidi Xu; Yanqiu Zhu; Xianxiang Wang (Food Bioscience, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

A narrow-bandgap organic photothermal material enabling efficient solar driven sustainable electricity-water cogeneration - Xiaoqing Liu; Bingpeng Guo; Rui Wei; Huijun Kong; Jiahui Yu; Baolei Wang; Weiyan Li; Jingyue Zhang; Chuanying Wang; Zhongqian Song; Changxiang Shao (Chemical Engineering Journal, 2026)

Polymer-based hydrogen barrier coatings: Material design, mechanisms, and theoretical simulation - Zhuofan Li; Zhibin Chen; Lingwei Ma; Jinke Wang; Xin Guo; Rui Tian; Bowei Zhang; Huaiyuan Wang; Dawei Zhang (Chemical Engineering Journal, 2026)

Bioinspired antibacterial hydrogel empowered by switchable cerium-based nanoreactors for infected diabetic wound healing - Pengqin Xu; Longbao Feng; Yakupu Aobuliaximu; Minjian Liao; Yuejia Wu; Qiong Li; Chunmao Han; Rui Guo; Xingang Wang (Chemical Engineering Journal, 2026)

Mesoporous carbon nanospheres-confined ZnMn2O4/Mn3O4 heterostructures for sustainable zinc-ion storage - Ling-Xin Kong; Songtao Zhang; Yaxun Hu; Peng Liu; Wanchang Feng; Zefan Sang; Xiaotian Guo; Hao Gong; Rui Wang; Dae Joon Kang; Huan Pang (Chemical Engineering Journal, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Dynamically structured bubbles enhance energy release performance in solar-driven carbonation reaction - Chao Song; Qiang Guo; Yinshi Li; Jinbo Che; Jiabin Fang; Qiang Xu; Tao Fan; Rui Wang (Chemical Engineering Journal, 2026)

Fracture development characteristics in carbonate reservoirs: insights from stress field simulation with a heterogeneous rock mechanics model and adaptive boundaries - Yao Wang; Wenlong Ding; Zhongliang Guo; Chenggang Li; Bochao Tang; Ziyou Zhang; Dong Fu; Rui Xia (Carbonates and Evaporites, 2026)

Oxygen demand and behavioral responses of adult largemouth bass (Micropterus salmoides) to intensive aquaculture-related drivers - Hao Fan; Chang Guo; Xiang Lei; Peng Wan; Ming Zhu; Deqing Wang; Rui Song (Aquacultural Engineering, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

A Novel Cancer Driver Genes Identification Method Based on Self-Supervised Dual Masked Graph Autoencoder - Pi-Jing Wei; Xinhao Guo; Wenjun Li; Yun Ding; Rui-Fen Cao; Zhenyu Yue; Kanglin Wang; Chun-Hou Zheng (Interdisciplinary Sciences: Computational Life Sciences, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Microbial niches and metabolism drive spatial heterogeneity of hydroxyapatite precipitation in aerobic granular sludge - Gonglei Wang; Fan Yang; Shanshan Xu; Dexin Lin; Rui Yang; Peng Yan; Youpeng Chen; Fang Fang; Jinsong Guo (Water Research, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Remote sensing of rural clean heating impacts on air quality: An STL-Q3 framework in Henan Province, China - Yongliang Yang; Wenqiang Guo; Zhitao Zhou; Kai Ji; Zhibin Lai; Rui Xu; Feiyang Wang; Linlu Mei (Remote Sensing Applications: Society and Environment, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Transcriptomic insights into the antifungal efficacy of Bacillus velezensis-synthesized silver nanoparticles against toxigenic fusarium verticillioides - Shumila Ishfaq; Xiaotong Gai; Xiaoyan Liang; Yi Ding; Rui Wang; Arslan Anjum; Yongzhan Cai; Amna Rafiq; Wei Guo (Pesticide Biochemistry and Physiology, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

Sleeper-induced pipeline buckling under non-uniform transient temperature field - Dongyang Liu; Zhenkui Wang; Haoyan Sun; Qian Zhang; Shengjie Rui; Lizhong Wang; Zhen Guo (Ocean Engineering, 2026)

Divergent microplastic assemblages across natural and artificial waters in the Wei River Basin - Yiping Guo; Zhe Liu; Houpu Ren; Zixuan Zhang; Shichen Wei; Guojin Qi; Taishuo Zhang; Rui Wang; Xinyu Xu; Peng Liu; Hanzhong Jia (Journal of Water Process Engineering, 2026)

Preparation of P507-containing monodisperse magneto-permeable polystyrene swelling microspheres for extraction of low-concentration scandium from simulated red mud liquor - Jie Wang; Jinghan Ren; Rui Feng; Chenxi Li; Chenxin Shi; Mingqi Guo; Tianlei Yang; Yueping Guan (Journal of Water Process Engineering, 2026)

CWN-Net: a precise segmentation model for composite water networks using multi-source and multi-temporal remote sensing imagery - Mingyang Li; Huimin Lei; Fulin Li; Jiwen Huang; Yuzhi Shi; Shangjie Xu; Han Wang; Sinan Wang; Rui Wang; Lili Liu; Suzhen Cheng; Lei Guo; et al. (Journal of Hydrology, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Resistome risks of biological wastewater treatment communities: A global dataset of activated sludge, anaerobic digestion, and anammox - Min Xu; Shengchun Qi; Xiaofan Yu; Shiyi Han; Rui Xiao; Jianhua Guo; Changzhi Wang; Ning Zhu; Huijie Lu (Journal of Hazardous Materials, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Micritization mechanism in penecontemporaneous carbonate rocks: coupled C − Ca cycles and constraints from diagenetic environments - Yunfeng Zhang; Menghao Zhu; Wen Yan; Haizhou Qu; Kexin Guo; Weihai Xu; Xiyang Zhang; Fei Tan; Yu Tang; Rui Wang; Guanghui Wu; Shuai Huang (Geochimica et Cosmochimica Acta, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Quinoa bran polyphenol extract ameliorates NAFLD through modulating Allobaculum and regulating pantothenate and CoA biosynthesis alongside retinol metabolism - Minjun Sun; Sarina Ma; Rui Wang; Ying Miao; Rui Huo; Qixin Gu; Wenhui Guo; Dongyan Li; Meili Zhang (Food Bioscience, 2026)

Geometry-programmed microcapsules for rice-leaf interface pinning and targeted fungicide delivery - Xiquan Ding; Lei Wang; Meng Yu; Hongwei Li; Yinmin Wang; Xinyu Guo; Yucheng Gu; Hongyan Zhang; Xuemin Wu; Rui Zhao; Yong Xu (Chemical Engineering Journal, 2026)

Oxygen-vacancy-rich Na2Ti3O7/Ti3C2Tx arrays via H2O2 etching for humidity sensors - Xinlu Zhao; Hang Yue; Chuanyu Guo; Xin Dong; Tingting Wang; Rui Gao; Xiaoli Cheng; Yingming Xu (Chemical Engineering Journal, 2026)

Increasing carbon emissions despite declining burned area in the Northern Hemisphere wildfires - Rui Shi; Yuhui He; Ruitong Guo; Xiaofan Wang; Yaliang Hou; Yue Zhou; Xiaoying Niu; Hui Wen; Jun Liu; Wei Pu; Xin Wang; Dongyou Wu (Atmospheric Research, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Higher nutrient availability fosters intricate bacterial networks in rhizosphere of invasive plants - Mengxin Zhao; Han Zhang; Qiao Li; Die Zhang; Jianying Guo; Rui Wang; Fengjuan Zhang; Fanghao Wan; Wanxue Liu (Applied Soil Ecology, 2026)

Lithium Enhances Survival Bias Associated with the Lateral Habenula Suppression - Kunlin Liu; Rui Zhu; Haoyue Guo; Jinghuan Li; Qianfu Wang; Yi He; Chenggang Zhu; Zheng Ma; Xiaodan Jiang; Jack van Honk; Jin Bao (Neuroscience Bulletin, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

A root cause diagnosis strategy based on error correction instantaneous granger causality algorithm for non-stationary industrial processes - Rui Chen; Yuan-Qiang Zhou; Li-Lan Liu; Jian-Guo Wang; Yuan Yao; Chen Peng (Process Safety and Environmental Protection, 2026)

Collaborative optimization of hydraulic PTO parameters for a double floating WEC: Integrating orthogonal design and Bayesian optimization - Jianwei Wang; Jiachen Chai; Xinyu Han; Minghua Yue; Ze He; Rui Guo; Wei Cai (Ocean Engineering, 2026)

Optimizing dual-active-site electrocatalysts for adsorption and hydrogenation for efficient nitrate-to-ammonia - Hui Xu; Peiquan Li; Jinghuan Peng; Tianju Chen; Rui Guo; Jinwu Hu; Jingcheng Xu; Jianping Yang; Ding Wang (Journal of Hazardous Materials, 2026)

Novel non-thermal plasma based strategy to synthesize high-performance multistage mesoporous cobalt-ceria oxides for plasma-catalytic decomposition of environmentally hazardous acetone - Lu Liu; Jian-hua Liu; Zhen-yun Wang; Guang-cai Shao; Yan-gang Hu; Karen Leus; Jian-li Mi; Chuan-long Ma; Rui-tang Guo; Qing-shan Wang; Anton Nikiforov; Pascal Van Der Voort; et al. (Journal of Hazardous Materials, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Distribution profiles of 12 isoflavone monomers in Chinese soybeans from saline-alkali and ordinary soils and subsequent supercritical CO₂ extraction optimization - Zixuan Liu; Ziqian Xue; Rui Yang; Xinru Guo; Yutong Zhen; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2026)

Generation and characterization of the monoclonal antibody against the heavy chain of American eel (Anguilla rostrata) IgM - Xiaolong Meng; Shuangshuang Cao; Hongjun Xie; Wenting Jiang; Rui Guo; Yuchen Zhuo; Qicheng Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2026)

Effects of heat input on heat-affected zone of simultaneously welded cruciform fillet joints in Q550D and Q690D steels - Yize Gao; Xiao-Ling Zhao; Yan-Bo Wang; Rui Yan; Zhe Sun; Guo-Qiang Li (Engineering Structures, 2026)

A model-data synergy framework for assessing and enhancing runoff control in sponge cities: Sensitivity-driven calibration and multi-tiered monitoring integration - Guorui Wu; Jia Guo; Nan Ni; Suhui Wang; Songwen Yang; Rui Wang; Liang Feng (Ecological Modelling, 2026)

Visible-light-driven N-CDs/Cu photocatalysis for CO2 valorization to selenylated vinyl oxazolidinones - Jun-Bo Wang; Jia-Tong Guo; Shu-Rui Wang; Bei Ruan; Zhan-Hui Zhang (Chemical Engineering Journal, 2026)

Sericin-bioinspired nanoplatform prevents bisphosphonate-related osteonecrosis of the jaw: synergistic mitochondrial modulation and microenvironmental restoration - Zhuoya Cui; Yuanyang Li; Kehong Guo; Hanrui Liao; Zitong Xia; Tao Wang; Rui Cai; Yao Wang; Gang Tao; Dan Zhao (Chemical Engineering Journal, 2026)

Upgrading H2/CO2-containing waste gas to single cell protein: Tolerance and response of Cupriavidus necator H16 to hydrogen sulfide - Jie Wang; Rui Li; Manqian Wang; Xuening Wang; Min Xue; Ankun Xu; Kai Luo; Xiaolei Fan; Rongbo Guo; Shanfei Fu (Chemical Engineering Journal, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Tailoring microstructure of cellulose-derived hard carbon by pre-oxidation for superior sodium-ion storage - Hairu Wang; Rui Ma; Qingtao Ma; Mengjiao Xu; Lili Ai; Dianzeng Jia; Luxiang Wang; Nannan Guo (Chemical Engineering Journal, 2026)

Multi-level design of a chitosan-based membrane: from sisal fiber reinforcement to surface micropatterning and hybrid hap for enhanced bone regeneration - Shuo Tang; Rui Lin; Yuqing Wang; Xinyuan Feng; Fang Shi; Yupeng Guo; Shu Huang; Xiang Hu; Liuyun Jiang (Carbohydrate Polymers, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

P2Y12-AMPKα2 signaling contributes to cardiomyocyte senescence in doxorubicin-induced heart failure - Qianqian Niu; Huidan Wang; Mengyao Zhao; Hongdou Zhang; Rui Hao; Peiyao Liu; Lijuan Guo; Bulei Chen; Yuting Xi; Peng Li; Yaling Yin (Molecular and Cellular Biochemistry, 2026)

Adaptive Fixed-Time Control Framework for Deterministic Response of Fully Constrained Vessels with Unknown Dynamics - Qiang Guo; Shuangpeng Duan; Jia Zhou; Shengguo Wang; Rui Li; Xianku Zhang (Journal of Marine Science and Engineering, 2026)
To achieve precise trajectory tracking for surface vessels subject to unknown dynamics, strict physical limitations, and external disturbances, this paper proposes an Adaptive Fixed-Time Control Framework that ensures a deterministic response under full constraints. First, navigation safety is guaranteed by employing a Barrier Lyapunov Function (BLF) to strictly confine vessel position states, enabling constrained position tracking without requiring prior knowledge of the desired trajectory. Second, addressing the input constraint aspect of the “full constraints” problem, a fixed-time auxiliary system is introduced to compensate for nonlinearities induced by actuator saturation, thereby maintaining control feasibility. Central to this framework is the realization of a deterministic response; by incorporating fixed-time convergence theory, the controller guarantees that velocity tracking errors converge within a predefined time bound independent of initial conditions. Furthermore, an RBF neural network combined with adaptive techniques is utilized to estimate unknown dynamics and external disturbance bounds online, enhancing robustness and safety in realistic marine environments.

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Low-dose nitrogen-doped carbon quantum dots boost medium-chain fatty acids production via enhanced proton-electron transfer - Shan-Shan Ye; Rui-Dong Xie; Yong-Yao Zhang; Qing-Lian Wu; Wei-Tong Ren; Hua-Zhe Wang; Juan-Shan Du; Wan-Qian Guo (Water Research, 2026)

Ascosphaera apis invasion alters the expression pattern, alternative splicing and alternative polyadenylation of transcripts in the eastern honeybee larval gut - Jianfeng Qiu; Fangji Wang; Xiang Li; Tao Wu; Xin Jing; Zhenzhen Zuo; Jing Tian; Dafu Chen; Rui Guo (Journal of Invertebrate Pathology, 2026)

Carbon-supported nZVI mediates Fe oxides-DOM interactions to regulate Cd and As bioavailability in co-contaminated soils - Jianhua Guo; Yan Wu; Heng Zhang; Rui Wang; Yue Zhao; Xin Fan; Shuaitao Feng; Zuben Xu (Journal of Environmental Chemical Engineering, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Exploring the link between PFASs exposure and gestational diabetes risk within the TRAEC framework - Jinzhao Ma; Rui Niu; Yupeng Wang; Shahan Mumtaz Khan; Mengan Guo; Anru Wang; Guizhen Du (Food and Chemical Toxicology, 2026)

Food-grade TiO2/TDCPP Co-exposure disrupts ACOD1/itaconate axis and is associated with TET2-NF-κB inflammation in microglia exacerbating neurotoxicity - Qing Guo; Duijuan Wang; Changning Zhao; Shirong Wei; Chenhan Hu; Zecheng Liu; Ying Li; Rui Li; Jinqiang Wang (Food and Chemical Toxicology, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Research on the Mechanisms Regulating Soil Microbial Community Structure and Functional Metabolism during Coloured Potato Cultivation with “Seed Rotation” - Yulong Wang; Anle He; Huachun Guo; Fang Yang; Youhan Li; Lei Bai; Jun Li; Rui Zhang (Potato Research, 2026)
To address the continuous cropping obstacles associated with coloured potatoes ( Solanum tuberosum L.) in the red soil region of Yunnan, in this study, two “seed rotation” cultivation regulation modes, namely cultivar rotation (red potato–purple potato) and crop rotation (red/purple potato–soybean), were innovatively proposed. Through pot experiments, the regulatory effects of different cultivation modes on soil nutrients, enzyme activities, microbial community structure, and functional metabolic networks were systematically analysed. Compared with the monocropping of a single potato cultivar, the cultivar switching treatment significantly improved the soil nutrient status, with the contents of soil available nitrogen, phosphorus, and potassium significantly increasing by 56.40–58.04%, 14.96–27.44%, and 58.59–62.21%, respectively, while the cultivar rotation treatment had a secondary effect. In addition, the interspecific rotation treatment enriched beneficial bacteria such as Bradyrhizobium ; upregulated the abundance of secondary metabolites, including flavonoids; and activated biosynthetic pathways such as those involving phenylpropanoids, flavonoids, and various amino acids. Compared with the continuous cultivation of a single potato cultivar, the cultivar rotation treatment alleviated the homogenization trend of the soil microbial community, increased the abundance of organic acids and glycosides, and activated pathways such as the shikimate pathway and the biosynthetic pathways of aromatic amino acids (phenylalanine and tyrosine). In summary, both modes, especially the interspecific rotation mode, can improve the soil environment and have significant agronomic application value and ecological environmental benefits. Owing to the similar biological characteristics between the same family, the cultivar rotation mode results in relatively limited changes in the soil microbial community and metabolite composition, but it can delay the occurrence of continuous cropping obstacles. This study provides practical value for the sustainable soil management of potato cultivation in red soil regions.

A comprehensive review on the main alkamides in Piper nigrum and anti-inflammatory properties of piperine - Rui Guo; Yiming Fang; Junyao Li; Haoyang Gao; Zhiqiang Niu; Yadong Lv; Long You; Ji Zhang; Xu Wang; Guiping Wu; Taoyun Wang; Weicheng Hu; et al. (Phytochemistry Reviews, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

A Novel ML–NWP Coupled Optimization Approach on a Reconstructed WRF Model - Hai Chu; Yuan Cao; Rui Wang; Jianming Xu; Lei Chen; Xuliang Fan; Shiqi Chen; Jianhai Guo; Junjing Wu (Journal of Meteorological Research, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Construction of a plasmid-based reverse genetics system for the rescue of shrimp infectious covert mortality nodavirus (CMNV) and use in deciphering the role of its B2 protein in regulating its cross-species infectivity - Zhenxin Zhao; Ting Xue; Jinwu Wang; Rui Xiao; Yue Zhang; Meiling Sun; Qingli Zhang; Huarong Guo (Aquaculture, 2026)

Physicochemical, microstructural, and Vis/NIR optical properties of kiwifruit during bruise-induced ripening - Youhua Bu; Shuai Li; Mingzhuang Lin; Chengxu Gong; Rui Wang; Wenchuan Guo (Postharvest Biology and Technology, 2026)

Occurrence and dietary risk assessments of polyethoxylated tallow amine in soybeans - Xinru Cui; Zhenjun Liu; Rui Yang; Minjie Li; Xinru Guo; Zixuan Liu; Ziqian Xue; Bei Fan; Zehua Ke; Chunmei Li; Fengzhong Wang (Journal of Hazardous Materials, 2026)

Mechanism and optimization of NaCl removal from soy sauce residue using low pressure superheated steam drying: Role of condensation and moisture migration - Xin Xu; Jian-Bo Liu; Jia-Cheng Guo; Zhi-Hong Xing; Rui-Fang Wang; Qing Xu (Food Chemistry, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Trade-offs between crop yield and soil organic carbon sequestration under straw return across cropping systems - Yufei Cui; Mengdi Yang; Xiao Yang; Rui Wang; Shengli Guo (Field Crops Research, 2026)

U-shaped multi-scale feature fusion network for three-dimensional geological modelling and uncertainty assessment - Yu Zhang; Rui Wang; Jian Chu; Mingchun Guo (Engineering Geology, 2026)

Dual-sided Pd functionalization of groove-textured CeO2 hollow microcages boosts room temperature NO2 sensing - Yan Tong; Pengkai Xing; Wenbo Ruan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Muhammad Ikram; Xue Bai; Qin Guo; Keying Shi (Chemical Engineering Journal, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Chemically modified bacterial cellulose–mediated fiber salting-out method for preparing tough hydrogels - Bei Zhang; Xin-Xin Chen; Xiao-Rui Ge; Xin-Ping Wang; Xiao-Hui Yao; Wei-Guo Zhao; Tao Chen; Dong-Yang Zhang (Carbohydrate Polymers, 2026)

Nitrogen and phosphorus limitation patterns of microbial nitrogen cycling traits in an arid soil - Hongfei Ji; Ying Wang; Rui Wang; Shengli Guo (Journal of Soils and Sediments, 2026)

Sustainable land use and agricultural management enhance arbuscular mycorrhizal fungal communities and soil health - Huaisong Wang; Juntong Zhu; Mingming Wang; Lei Zhang; Ying Gao; Lianxuan Shi; Jixun Guo; Rui Guo; Tao Zhang (Applied Soil Ecology, 2026)

Corrigendum to “Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling” [Tissue and Cell, 97 (2025) 103089] - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2026)

Experimental and numerical investigations on hysteretic behaviour of tapered RAC-filled high-strength double-skin steel tubular columns - Yupeng Guo; Rui Wang; Hui Zhao; Yunhe Wang; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Curcumin-derived smart anti-corrosion coating for early damage warning and active protection in diverse lighting and corrosive environments - Jinke Wang; Xin Guo; Congshu Huang; Danni Shang; Zhibin Chen; Rui Tian; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2026)

Improved corrosion resistance of amorphous-containing dual-structured micro-arc oxidation coatings on (Zr0.5Ti0.35Nb0.15)90Al10 high-entropy alloy - Luqi Chai; Xuehui Yan; Yubo Ma; Lijiao Wang; Xin Li; Chungang Guo; Chi Xu; Jiancheng Du; Xiaoyue Jin; Wenbin Xue; Menglu Zhang; Rui Zuo (Chemical Engineering Journal, 2026)

Defect-rich 3D flower-like SnS2-xSex nanostructures for ultrasensitive NO2 gas sensing at room temperature - Shanshan Cong; Pengkai Xing; Wenbo Ruan; Jiahui Fan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Qin Guo; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

A room-temperature wireless NO2 gas sensor enabled by WO3 modified V2CTx nanosheets - Haineng Bai; Rui Guo; Yixin Zhou; Cheng Feng; Yiru Chen; Shengjie Zhang; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Myricetin alleviates myocardial infarction-induced cardiac fibrosis in mice by upregulating SIRT1 to inhibit TGF-β1/Smad2/3 signaling - Xiaojv Xiong; Rui Dai; Guangji Wang; Xin Guo; Qin He; Jijun Liu; Gang Chen; Pan Lu; Shuang Li; Denghai Liu; Jinhua Liu; Manhua Chen (Molecular & Cellular Toxicology, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

African swine fever virus pNP419L inhibits host translation and increases viral replication through the PERK/eIF2α pathway - Xueying Wang; Zixuan Wang; Yilin Guo; Sai Niu; Rui Liang; Lin Cheng; Hakimeh Baghaei Daemi; Guiqing Peng (Veterinary Microbiology, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Mechanistic insights into low-temperature NH3-SCR over Mn-based Zr-pillared montmorillonite (Mn/Zr-PILM): Synergistic catalysis revealed by experiments and DFT - Ziwen Zheng; Huaqing Xie; Zhenyu Yu; Bin Xiao; Qingbo Yu; Kun Wang; Jiabo Zhao; Haijian Xu; Rui Guo (Process Safety and Environmental Protection, 2026)

Integrated metabolomics and transcriptomics analyses reveal the molecular mechanism of anthocyanin accumulation in veins and leaves of Broussonetia papyrifera under cold stress - Xiangxue Yu; Rui Ni; Dingguo Zhang; Bo Chen; Qian Li; Ziyu Yang; Chenjing Li; Fuyuan Liu; Yongtao Xia; Guoqing Hou; Guoping Wang; Pengzhi Mao; et al. (Plant Science, 2026)

Evaluating the environmental impact of hydrothermal cracking solid organic fertilizer: Carbon and nitrogen retention and toxic metals analysis - Rui Xia; Xiao-xiao Yang; Jue Wang; Kai-le Li; Zhi-peng Sun; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Journal of Environmental Sciences, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Advancing screening of aquatic persistent, mobile, and toxic substances via integration of graph convolutional networks and multitask learning - Yang Chen; Rui Qiu; Jin Yin; Jingquan Wang; Peng Chen; Liping Luo; Hongguang Guo (Environmental Research, 2026)

Prenatal air pollution exposure and postpartum glucose intolerance in women with gestational diabetes mellitus: Identifying susceptible windows - Gaojie Fan; Qing Liu; Li Zhang; Jing Peng; Li Wu; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; et al. (Environmental Research, 2026)

Regulating water-salt transport in subsided soil reclamation: The mechanism of calcination-acid leaching activated coal gangue - Guiyuan Wang; Junmeng Li; Chenyang Li; Yanli Huang; Yachao Guo; Laiwei Wu; Pucheng Rui (Environmental Research, 2026)

Parallelization of the estuarine saltwater intrusion numerical forecast model UFDECOM-i using Fortran DO CONCURRENT - Hongyuan Guo; Bingrui Chen; Rui Ma; Yihe Wang; Jianrong Zhu (Environmental Modelling & Software, 2026)

Rewiring (p)ppGpp metabolism for high-yield anaerobic methanol and CO2 conversion in Butyribacterium methylotrophicum - Yuanke Guo; Feiyi Zhuang; Rui Zhang; Ruirui Qin; Jiao Feng; Kequan Chen; Xin Wang (Chemical Engineering Journal, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

pH-responsive dual MOF-on-MOF core-shell nanocarrier enables an innovative “pesticide–fertilizer integration” strategy for advanced plant disease management - Yingjian Ma; Pengkun Yan; Xiangdong Li; Meng Yu; Shouhe Pan; Yinmin Wang; Rui Zhao; Xinyu Guo; Yucheng Gu; Yong Xu; Xuemin Wu (Chemical Engineering Journal, 2026)

The enhanced role of glycine in methanesulfonic acid-methylamine-driven nucleation in urban aerosols and coastal industrial regions - Shuqin Wei; Kaiyu Xue; Xiaokai Guo; Wenyuan He; Tianlei Zhang; Rui Wang (Atmospheric Environment, 2026)

Integrating Machine Learning and Petrophysical Data for 3D Ore Body Modeling: A Case Study of the Bayan Obo Deposit - Shupeng Lu; Ya Xu; Rui Guo; Song Huang; Qianwen Zhang; Yonggang Zhao; Yun Liu; Jian Wang; Liang Zhao (Pure and Applied Geophysics, 2026)

Research on rock mechanics parameter prediction based on the frequency spectrum characteristics of vibration while drilling - Jia-kang Song; Jian-ning Wang; Zhao Ma; Yi-guo Xue; Rui-rui Cai; Fan-meng Kong; Lei Gao (Applied Geophysics, 2026)

Genomic evidence resolves species identity and hybridization in farmed Golden pompano (Trachinotus anak) - Liang Guo; Siqing Wang; Jiehong Wei; Rui Peng; Zhongyuan Shen; Luojing Zhou; Jiaxuan Kang; Ke Rao; Yang Yang; Zhennian Chen; Chang Wu (Aquaculture, 2026)

CoFe2O4/Sepiolite as a heterogeneous catalyst for peroxymonosulfate activation: Efficient tetracycline degradation, mechanism, pathway, and toxicity assessment - Rui Li; Xiaolong Hu; Kexin Wu; Runa Hou; Mengxiang Hui; Bohao Liu; Junying Song; Li Wang; Qingbin Guo; Dengzheng Gao; Qingbiao Wang; Lin Li (Journal of Water Process Engineering, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Comparative effects of raw and aged tire microplastics on anaerobic fermentation of excess sludge - Kai Hu; Hao Ding; Wei Wang; Rui Guo; Wei Chen; Hang Xu (Journal of Hazardous Materials, 2026)

Biodegradable microplastics induce more soil nitrous oxide emission than conventional in semi-arid Loess Plateau - Xiaogang Li; Rui Wang; Xinran Zhang; Shengli Guo; Lei Yu; Xiaotang Ju (Journal of Hazardous Materials, 2026)

Elucidating the complex food sources and biomagnification of hydrophobic and proteinophilic persistent organic pollutants in wetland birds from a tropical island - Yujing Zhu; Bei Cai; Jichao Wang; Rui Guo; Li Jian; Xiaobo Zheng; Bixian Mai (Journal of Hazardous Materials, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Investigation of water and oxygen influence on the coal thermal decomposition entire process kinetic mechanism and gas product source tracing - Xin-xiao Lu; Guo-yu Shi; Rui-nan Zhang; Shuo Wang; Long He; Guan Wang (Fuel, 2026)

Tailoring a simplified and steady-state kombucha consortium for newly-formulated kiwifruit beverage production: Impacts on untargeted/targeted metabolites, antioxidant capacities and flavor profiles - Shiqi Li; Keying Chu; Rong Guo; Jiamin Wu; Xingnan Wang; Jing Guo; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2026)

Strain-dependent immunomodulatory activities of lipoteichoic acids from probiotics: From interspecies to intraspecies variation - Yini Liu; Rui Xiao; Min Guo; Jingyu Lu; Jianxin Zhao; Ruojie Zhang; Hao Zhang; Gang Wang; Zipei Zhang (Food Bioscience, 2026)

Integrating field surveys and visual interpretation to enhance CSLE model of soil erosion response to LUCC in Southwest China - Rui Tan; Geng Guo; Kaiwen Huang; Zicheng Liu; Chaorui Wang; Jie Lin; Yizhong Huang (Environmental Modelling & Software, 2026)

Alkali-induced molecular aggregation enabled rapid-forming PVA hydrogel electronic skin with multifunctional integration of protection, EMI shielding, and sensing - Di Liu; Yang Lyu; Zhongying Ji; Rui Guo; Zhihan Hong; Xiaolong Wang; Xinyan Shi (Chemical Engineering Journal, 2026)

Understanding the migration and transformation characteristics of Cr3+ in the hydrothermal cracking of biomass model components - Rui Xia; Kai-le Li; Peng Zhao; Xiao-xiao Yang; Jue Wang; Ke-wen An; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Biomass and Bioenergy, 2026)

A new isoflavone from processed root barks of Paeonia suffruticosa and their procoagulant activity - Shuo-Guo Li; Rui Yang; Mi-Mi Lu; Shu-Mei Wang; Jiang Meng (Natural Product Research, 2026)

Unraveling Successional Trajectories of Functional Microorganisms and Sulfur-Mediated Metabolic Pathways in Advanced Nitrogen Removal of Tannery Wastewater - Rui Fang; Huixue Ren; Ning Guo; Yan Jin; Weichun Liang; Chen Wei; Liya Wang; Shubing Han (Water, Air, & Soil Pollution, 2026)

Patterns of phoD- and pqqC-containing bacterial communities and their potential linkages with soil P cycle multifunctionality under long-term crop rotations - Hongfei Ji; Yan Chen; Ying Wang; Rui Wang; Shengli Guo (Plant and Soil, 2026)

Genetic Parameter Estimation of Growth Traits and Their Implications for Selective Breeding in Small Yellow Croaker (Larimichthys Polyactis) - Rui Wang; Jiajie Zhu; Sifang Liu; Ting Ye; Dandan Guo; Yang Liu; Bao Lou; Feng Liu (Marine Biotechnology, 2026)

Pseudomonas eutrophicaquae sp. nov., a novel xenobiotic-degrading non-motile bacterium, containing Q-8 ubiquinone, isolated from an aquatic ecosystem in Jimo District, China - Kaiyue Wang; Jinhua Hu; Ke Ma; Haoran Liu; Doudou Kang; Mengyang Li; Jianjun Song; Bai Guo; Shuzhen Wei; Aijv Liu; Rui Zhang; Fengtang Yang; et al. (Antonie van Leeuwenhoek, 2026)

Influences of topography changes on the evolution of salinity intrusion in the North Branch of the Yangtze River Estuary over the past 70 years - Rui Ma; Zhilin Zhang; Yidi Yang; Zhigang Guo; Jianrong Zhu; Yihe Wang (Frontiers in Marine Science, 2026)
Estuarine topography influences hydrodynamics and salinity intrusion. The most significant feature of salinity intrusion in the Yangtze River Estuary is the salt-spilling-over (SSO) into the South Branch from the North Branch (NB), which affects the utilization of freshwater resources in the South Branch where three reservoirs were built. The topography in different decades from the 1950s to the 2020s was collected, and a numerical model was adopted to simulate the topography changes on salinity intrusion and SSO. From the 1950s to the 2020s, the topography of the Yangtze River Estuary changed greatly, especially in the NB. The channel area of the NB decreased by 55.56%, and its channel volume decreased by 57.57%. The numerical simulation results showed that the evolution of salinity intrusion in the NB and SSO experienced weakening–enhancing–weakening processes. The NB was covered by high-salinity water and experienced the SSO in the 1950s. The SSO distinctly weakened in the 1970s and 1980s, greatly enhanced in the 1990s, reached its most severe level in the 2000s, and significantly weakened in the 2010s and 2020s. From the 1950s to the 2020s, the tidal prism of the NB constantly decreased, with a reduction of 62.32% during spring–neap tide. The variations in the net water flux, net salt flux, and water diversion ratio in the upper section of the NB were consistent with the evolution processes of SSO. The evolution mechanisms of the salinity intrusion and SSO were elucidated in view of changes in the estuarine topography and dynamic factors.

Fabrication of Rare Earth-Doped Fe3O4/HAP Nanoparticles with Fluorescence and their Application in Food and Beverage Testing - Yulin Wang; Rui Wu; Yankun Zhang; Guanghui Tian; Jiawei Guo; Yapeng Li (Journal of Fluorescence, 2026)

Mechanism of Chain Rockbursts in Deep Excavations Triggered by Dynamic Disturbance: Insights from Stress Path Controlled Failure - Biao Wang; Ben-Guo He; Xiang-Rui Meng; Hong-Pu Li; Zhao-Tong Jin (Rock Mechanics and Rock Engineering, 2026)

Effect of environmental factors on the control of milky disease in Chinese mitten crab (Eriocheir sinensis) - Rui Zhang; Zhigang Zhao; Kun Guo; Xu Zhao; Xiangyi Deng; Shihui Wang; Liang Luo (Aquaculture, 2026)

Path to sustainable marine development: Does artificial intelligence development in coastal regions matter for green growth in the marine economy? Evidence from China - An Yan; Rongjie Guo; Qiaorong Yin; Rui Dong; Xinbin Wang; Lehua Gao (Regional Studies in Marine Science, 2026)

Enhanced rock-breaking performance of an angular Helmholtz cavitation jet nozzle: Flow field dynamics and mechanism analysis - Chenrui Guo; Rui Li; Hao Wang; Zhongwei Huang; Gensheng Li; Huan Li; Jingbin Li; Jiaqing You (Process Safety and Environmental Protection, 2026)

Numerical study of three-dimensional pull-out capacity and structural optimization for dynamically installed anchors - Haojie Zhang; Lizhong Wang; Shengjie Rui; Hongyu Wang; Zhen Guo (Ocean Engineering, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

High-performance composite adsorbent for the identification and enrichment of fenthion and its main metabolites - Lingjun Geng; Pengwei Zhang; Qingxia Han; Haifang Wang; Jingcheng Huang; Rui Xu; Jicheng Zhao; Yemin Guo; Xia Sun; Fangling Du (Journal of Hazardous Materials, 2026)

Zoning-grading optimization of watershed ecological security network integrating function and structure: A case study in the Three Gorges Reservoir Area - Dan Chen; Kai-rui Guo; Wei Zeng; Fu-hai Wang (Journal of Cleaner Production, 2026)

Research on the failure modes of frozen loess under uniaxial compression with varying moisture contents - Yuan Xin; Qiang Sun; Pingye Guo; Jingjing Nan; Jishi Geng; Ziyu Wang; Rui Lv; Shaoli Liu (Journal of Applied Geophysics, 2026)

Photocatalytic carbon dots for food-borne hazards: Antimicrobial and degradation mechanisms and applications in the food industry - Dangfeng Wang; Wangqing Jiang; Likun Ren; Yang Jiang; Yuqiong Meng; Rui Ma; Shulin Wang; Hongyan Guo; Fangchao Cui; Xuepeng Li; Tingting Li; Jianrong Li (Food Research International, 2026)

Associations of outdoor artificial light at night exposure with telomere length and mitochondrial DNA copy number in children and adolescents: Examining sex-specific associations - Gaojie Fan; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; Liqin Hu; Xiaoning Lei; Youjie Wang; Mingyang Wu; et al. (Environmental Research, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Synergistic 3d-5d orbital interactions on oxygen vacancy-rich Pt/TiO2 for enhanced photothermal catalytic oxidation of propylene - Xiaoxiao Zhu; Weidong Yuan; Siyi Song; Tong Chen; Wenjun Xiong; Sibo Wang; Jinpeng Hu; Rui Liu; Zhu Luo; Jinlong Wang; Ang Gao; Yanbing Guo (Chemical Engineering Journal, 2026)

Influence of coal dust on flame propagation characteristics and spectral features of gas explosion - Qiuhong Wang; Zezhou Song; Jun Deng; Zhenmin Luo; Wei Gao; Yating Zhang; Guoqiang Dong; Rui Guo; Di Wu (Chemical Engineering Journal, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

ZmDRZ1 negatively regulates drought tolerance via modulating ABA signaling pathway in maize - Zhifeng Chen; Yuhang Guo; Xiaodong Wang; Jian Li; Rui Li; Yang Qin; Yiru Wang; Jun Zheng (Plant Cell Reports, 2026)

Mechanistic Integration of Beta-Alanine–Carnosine Buffering and Glutamine Metabolism in Exercise-Induced Muscle–Brain Crosstalk: Implications for Aging, Neurodegeneration, and Cognitive Decline - Rui Wang; Yan Guo; Juan Li; Tian Peng; Xinghao Wang (Molecular Neurobiology, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

Per- and polyfluoroalkyl substances in China’s wastewater, surface water, and groundwater: occurrence characteristics, spatiotemporal distribution, and risk assessment - Qinru Wang; Rui Qiu; Yang Chen; Youqi Tao; Qi Zhou; Hongguang Guo (Environmental Geochemistry and Health, 2026)

Integrated assessment reveals plowing/no-tillage rotation as the trade-off considering crop yield and environmental performance in the Loess Plateau - Xingyu Guo; Shulan Wang; Hao Wang; Naeem Ahmad; Xiaoli Wang; Jun Li; Rui Wang (Agricultural Systems, 2026)

Multiscale analysis of the spatiotemporal evolution of carbon emissions in China from 2000 to 2020 based on the DMSP-OLS and NPP-VIIRS nighttime light data - Rui Liu; Decheng Wang; Runcan Han; Xirong Guo; Jialiang Han; Kai Cao; Xin Pan; Juncheng Gou (Advances in Space Research, 2026)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

Adaptive backward-correction extended Kalman filter for small amounts of measurement data - Chaofeng Lan; Rui Guo; Jintao Yang; Huan Chen; Jinghan Wang (Ocean Engineering, 2025)

A new risk for the recovered Tibetan antelope (Pantholops hodgsonii): Co-exposure of microplastics with organophosphates in their habitats - Rui Guo; Caian He; Jian Sun; Shaohua Li; Chuntao Zhao; Zhiyong Ling; Liang Chen; Wenrui Zhang; Jingmeng Li; Bing Wang; Jufang Hu; Dongmei Yu; et al. (Journal of Hazardous Materials, 2025)

Grazing disturbance reduces soil organic carbon sequestration and stability in desert steppe - Naijing Lu; Tianqi Zhao; Jianying Guo; Mengli Zhao; Guodong Han; Zhongwu Wang; Jiangfeng He; Rui Zhao; Yong Wang; Jian Guan; Bin Zhang; Guang Yang (Journal of Environmental Management, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Single-atom Pt-engineered TiO₂ photoanode enabling low-charge voltage and high-efficiency neutral Zn-air batteries via photoelectrochemical enhancement - Wenliang Wang; JiangYuan Qiu; Tao Yu; Shuming Zhang; Xingwang Niu; Rui Guo; Jinsheng Li; Xuanwen Liu (Journal of Environmental Chemical Engineering, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Esculetin improves lipid metabolism disorders induced by a high-fat diet by regulating the P13K-AKT signaling pathway and taurocholic acid metabolism - Liyang Guo; Yongjie Zhang; Kun Wang; Shun Wang; Yecheng Yao; Weiqi Liu; Fuhua Gu; Yifan Li; Rui Li; Jichang Li; Chunli Chen (Food Research International, 2025)

Novel carbon dots-based system for “on-off-on” fluorescence consecutive sensing of Au3+ and L-Cys - Guo Wei; Chuanliang Wang; Rui Wang; Xuhui Geng; Jinhua Li; Lingxin Chen; Zhihua Song (Food Chemistry, 2025)

LAB-fermented soy protein gels alleviate soy allergy through a novel dual mechanism: Coordinated intestinal barrier fortification and site-specific allergen degradation - Yaqiong Wang; Xinran Guo; Jie He; Haijun Wang; Runqiang Yang; Wei Li; Xin Rui (Food Bioscience, 2025)

Integrated untargeted metabolomics and physiological analysis reveal the response mechanisms of Procambarus clarkii larvae to carbonate alkalinity exposure - Kun Guo; Zhigang Zhao; Rui Zhang; Liang Luo; Shihui Wang; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Dual pH/glutathione-responsive polyphenol-based self-assembled nanoparticles loaded with lambda-cyhalothrin show enhanced UV stability and non-target organism safety - Lei Wang; Zheng Zhang; Yu Fang; Rui Zhao; Shouhe Pan; Meng Yu; Yinjie Ma; Yinmin Wang; Xiquan Ding; Xinyu Guo; Fengyu Li; Pengkun Yan; et al. (Chemical Engineering Journal, 2025)

3D printed hydrogel with fingerprint-inspired features for enhanced sensing performance in electronic skin - Jianshe Hao; Yanbin Xu; Chaofan Yang; Rui Guo; Yang Lyu; Zhongying Ji; Xiaolong Wang (Chemical Engineering Journal, 2025)

Dual-functional 3D-printed polyetheretherketone scaffolds with immunomodulatory nano‑calcium silicate/interleukin-4 coating synergistically enhance osteogenesis through macrophage M2 polarization and NF-κB pathway suppression - Xiaoyu Guo; Yanwen Su; Zixuan Wu; Zidong Wu; Kaili Liu; Junyu Yue; Yuning Qu; Kunzheng Wang; Jiankang He; Rui Ma; Pei Yang (Chemical Engineering Journal, 2025)

Protection against intestinal damage in female Drosophila melanogaster: Comparative contribution of arabinoxylan and its non-covalent/covalent complexes with catechin - Dima Atehli; Tianyu Qi; Rui Liu; Wan Wang; Qiaomei Zhu; Yuanlin Sun; Qingbin Guo; Ji Kang (Bioactive Carbohydrates and Dietary Fibre, 2025)

Integration of transcriptome and metabolome analysis reveals that alternative splicing of TT8 modulates anthocyanin biosynthesis in postharvest blood orange stored at moderate temperature - Wang Jianhui; Xu Rui; Guo Weiqing; Li Zhihong; Liu dayu; Li Jingjing; Li Dagang; Chen Ying (Plant Molecular Biology, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

TROAP aggravates chemoresistance of colorectal cancer cells via lipogenesis by PI3K/Akt pathway and histone acetylation - Ling-Ling Wang; Rui Zhang; Ning Li; Zheng-Guo Cui; Hua-Chuan Zheng (Functional & Integrative Genomics, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

A systematic review of montmorillonite-asphalt composite materials: Green clay mineral-reinforced asphalt for sustainable pavement solutions - Hao Lai; Anhua Xu; Jianliang Zhai; Youjie Zong; Wei Deng; Haoyan Guo; Bowen Guan; Mingfeng Chang; Rui Xiong; Zhenjun Wang (Applied Clay Science, 2025)

Formaldehyde emissions in tanker truck cabins: Observation, deep learning prediction and health risk assessment - Rui Zhang; Dongdong Guo; Ruixiu Jiang; Honglin Cao; Yunjia Wu; Lirong Kou; Meng Wang; Linwei Xi; Yang Liu; Haimei Wang; Jianyin Xiong (Science of The Total Environment, 2025)

Prevalence and risk factors of Giardia duodenalis in sheep and goats in global: A systematic review and meta-analysis - Zhengyi Li; Wei Wei; Yuan Ma; Luyao Hao; Yuan Guo; Rui Wang (Preventive Veterinary Medicine, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Future and present susceptibility to thermokarst hazards in the Northern Hemisphere using an interpretable CNN method - Yuting Yang; Rui Wang; Nan Guo (Journal of Hydrology, 2025)

Insights into the key odorants in Chimonanthus praecox var. concolor Mak. Flower using the sensomics approach - Peng Guo; Wei Guan; Runhu Xin; Yuanhao Zhou; Miao Liang; Yajian Wu; Rui Wang; Yuping Liu (Food Chemistry, 2025)

Study on the distribution characteristics and toxic risks of trace elements in the eggs of green turtles (Chelonia mydas) nesting on the Xisha Islands - Xiang Li; Li Jian; Minyu Fu; Henyi Zhang; Yuxin Zhang; Rui Guo; Jichao Wang (Environmental Research, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

The synergistic effect of triazine-N and secondary amine-N anchors iodine species with MXene composite cathode for stable aqueous Zn–I2 battery - Jing Ma; Yaoyao Linghu; Kai Yuan; Rui Zhou; Hui Gao; Peihua Zhao; Shaohui Guo; Huiqi Wang; Yongping Qu; Chao Shen; Keyu Xie (Chemical Engineering Journal, 2025)

Self-sustaining one-step synergy of ultrasound-enzyme-ethanol for high-efficiency saponin production from waste Xanthoceras sorbifolium leaves - Huan Long; Rui Guo; Wangsheng Zhu; Fuliang Cao; Erzheng Su; Jiahong Wang (Biomass and Bioenergy, 2025)

Multifunctional fluorescent sensors N/CDs@Eu-MOFs for rapid detection of childhood obesity and acute myeloid leukemia biomarkers and identification of chiral enantiomers of lysine - Liping Peng; Rui Xue; Henglong Ren; Borong Ren; Mingyue Wang; Xiuli Niu; Hao Guo; Wu Yang (Analytica Chimica Acta, 2025)

Bidirectional associations between kidney function decline and carotid plaque progression: a longitudinal cohort study in the context of predictive, preventive, and personalised medicine - Jinqi Wang; Xiaoyu Zhao; Rui Jin; Zhiyuan Wu; Yanchen Zhao; Yunfei Li; Yueruijing Liu; Shuo Chen; Xiuhua Guo; Lixin Tao (EPMA Journal, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Impact of calcium alginate gel-urea modified dry water on free radical spectral signatures and suppression mechanisms in methane explosions - Bin Peng; Qiuhong Wang; Jun Deng; Chi-Min Shu; Guoqiang Dong; Qingfeng Wang; Chao Ma; Rui Guo; Jianxiong Liu (Process Safety and Environmental Protection, 2025)

Feasibility of reducing the capacity of plain reservoirs through the joint optimal scheduling of mountain and plain reservoirs - Dingrong Zhai; Aijun Guo; Yimin Wang; Jianxia Chang; Yibin Liang; Zhehao Li; Jingyao Sun; Zhentao Tang; Rui Zheng (Journal of Hydrology, 2025)

Diagnostic early freeze onset in the Bering Sea - Weibo Wang; Jie Su; Junpeng Zhang; Rui Ding; Chunsheng Jing; Xiaogang Guo (Journal of Marine Systems, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Sustainable enzyme immobilization: Enhanced antibiotics removal via dopamine-mediated CLEAs anchoring on porous sponge carriers - Keshuai Liu; Shuxian Zhang; Lingling Yang; Xiaoxuan Fan; Xiaofei Wang; Wangyan Zhao; Rui Mai; Xiaoli Guo; Xueqin Ma; Guoning Chen (Journal of Environmental Chemical Engineering, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Effects of re-enter water on antioxidant, immune, intestinal flora and metabolome of Chinese mitten crab (Eriocheir sinensis) after high temperature air exposure - Xiangyi Deng; Yuhong Yang; Zhiqiang Li; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

ROS-responsive hydrogel loaded with berberine liposome protects against intervertebral disc degeneration by inhibiting mitochondrial fission and apoptosis - Cunliang Guo; Lilong Du; Xiaoxun Du; Rui Gao; Xinyi Jiao; Zhenhua Li; Tongxing Zhang; Pingsheng Huang; Chuangnian Zhang; Zujian Feng; Weiwei Wang; Baoshan Xu (Chemical Engineering Journal, 2025)

Global response of soil phosphatase activity to land reclamation and vegetation restoration - Huaisong Wang; Mingming Wang; Jialing Xu; Yibo Tian; Jinyu Bai; Lei Zhang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; Rui Guo; Tao Zhang (CATENA, 2025)

Differential responses in topsoil and subsoil: N2O, CO2, and CH4 dynamics under extreme rainfall - Mengdi Yang; Yufei Cui; Xiaomin Li; Ning Zhang; Shengli Guo; Rui Wang (CATENA, 2025)

Silkworm sand-based bio-organic fertilizers reshape rhizosphere microbiomes and modulate soil chemistry for sustainable management of Myrica rubra decline - Leidong Hong; Chunlai Hong; Weijing Zhu; Fengxiang Zhu; Weiping Wang; Tao Zhang; Rui Guo; Xingjiang Qi; Xiuqin Zou; Yanlai Yao (Plant and Soil, 2025)

BDNF Alleviates Noise-Induced Cochlear Synaptopathy Through Inhibition of Autophagy - Fei Wang; Qianru Yu; Yangtuo Luo; Rui Guo; Liyuan Wu; Xinyu Song; Yang Li; Shuna Li; Ke Liu; Xuejun Jiang (Molecular Neurobiology, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

Hawthorn Polysaccharide Enhances Growth, Immunity, and Intestinal Health in Crucian Carp (Carassius auratus) Challenged with Aeromonas hydrophila - Liang Luo; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Cheng Zhao; Baoquan He; Wei Wang; Wenhua Wu (Fishes, 2025)
Bacterial disease infections pose a major challenge to the healthy growth of crucian carp. Hawthorn polysaccharide (HP) is a natural active ingredient in hawthorn and has a wide range of pharmacological effects. However, the mechanism of HP against Aeromonas hydrophila infection in crucian carp cultures is unknown. In this study, it was found that 0.4% HP could significantly reduce the mortality of crucian carp, significantly increase the activities of T-AOC, SOD, CAT, and GSH-PX of crucian carp infected with A. hydrophila (p

Unraveling the impact of COVID‑19 on Beijing’s subway system using a causal machine learning analysis - Linmu Zou; Yanhua Chen; Rui Guo; Peicheng Wang; Yanrong He; Shiyu Chen; Zijia Wang; Jiming Zhu (Sustainable Cities and Society, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

New point mutations in osmosensing two-component histidine kinase gene associated with iprodione resistance in Monilinia fructicola field isolates from China - Qian Long; Yiyi Guo; Miaomiao Yi; Changsheng Lu; Rui Zhong; Hao Zhang; Usama Amin; Dufang Ke; Zongwen Wang; Fengping Chen (Pesticide Biochemistry and Physiology, 2025)

Mechanistic insights into microbial-mediated transformation of Fe2+, Mn2+, and NH₄+ under co-existing conditions in groundwater: Evidence from two-dimensional tank experiment - Li Meng; Rui Zuo; Jingrui Wang; Xueru Guo; Jiawei Liu; Ziyi Wu; Jinsheng Wang; Yuanzheng Zhai; Zhigang Zhang; Xi Yang; Guanlan Wu (Journal of Water Process Engineering, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

A ratiometric fluorescent sensor based on Eu3 + -β-diketone functionalized covalent organic framework hybrid material-loaded in electrospun polyvinylidene fluoride film for ultra-sensitive and rapid detection of glyphosate - Yingfei Hui; Hao Guo; Rui Xue; Mingyue Wang; Yanyan Ma; Dengke Zhuang; Wu Yang (Journal of Hazardous Materials, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

The gastrointestinal digestion fates and postprandial plasma fatty acid profiles of four dietary lipids with different unsaturated levels: A comparative study using Sprague-Dawley rats - Yanjun Guo; Zhan Ye; Yanjun Liu; Jiaying Yan; Rui Li; Yanan Wang; Yuanfa Liu (Food Bioscience, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Electrochemical CO2 reduction via strain-engineered AuPd alloy catalysts - Shangdong Ji; Qian Wang; Jiapeng Huang; Ruiyun Guo; Yanan Li; Yangzi Zheng; Rui Li; Yaohui Zhao; Chao Wu; Mingshang Jin (Chemical Engineering Journal, 2025)

Conduction of AgNPs with different surface charges in pine trees and their prevention and control of pine wood nematode disease - Shouhe Pan; Pengkun Yan; Rui Zhao; Fengyu Li; Lei Wang; Yinmin Wang; Ze Lv; Yingjian Ma; Meng Yu; Xinyu Guo; Yonggang Xia; Yong Xu; et al. (Chemical Engineering Journal, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

BaTiO3 dressed in carbon multifunctional layer achieving high areal capacity zinc metal batteries - Rui Wang; Jing Xu; Shijun Luo; Yan Guo; Baohe Yuan; Lei Xu; Junming Li; Yongqi Zhang; Yusheng Wang; Wenpeng Yang; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

Enhancing flame retardancy and mechanical properties of epoxy/carbon fiber composites via a metal-phosphorus synergistic interface structure - Dou Hu; Guo-rui Zhang; Xiao-dong Qi; Jing-hui Yang; De-xiang Sun; Yong Wang (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Nitrogen fertilization management is required for soil phosphorus mobilization by phoD-harboring bacterial community assembly and pqqC-harboring bacterial keystone taxa - Lin YANG; Runze WANG; Jingwei SHI; Rui WANG; Shengli GUO (Pedosphere, 2025)

Dynamic compensation operating rule of parallel reservoirs to enhance sufficient hydrological and reservoir capacity compensation - Zhentao Tang; Xiaoya Deng; Aijun Guo; Yimin Wang; Jianxia Chang; Yibin Liang; Zhehao Li; Dingrong Zhai; Rui Zheng (Journal of Hydrology, 2025)

The feasibility and prospects of coal mine water as a cooling medium for data centers - Zaining Li; Chunhui Zhang; Peidong Su; Guifeng Zhao; ZePeng Wang; YiYun Li; YanXin Li; Mengna Wang; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Chemical Engineering, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

Contrasting leaf nutrient-hydraulic relationships between karst and non-karst forests - Chun-Yan Wan; Jun-Rui Yu; Zhong-Guo Li; Yong-Qiang Wang; Shi-Dan Zhu (Plant and Soil, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Exploring Core Genes Involved in Ischemic Stroke and the Therapeutic Potential of Hyperbaric Oxygen: Insights from Transcriptomic Analysis - Yingcun Bao; Xudong Guo; Jinhai Wang; Jihe Kang; Rui Ma; Xiaorong Cheng; Yumei Ma; Yanxia Niu; Wei Zhang; Xiaoling Li (NeuroMolecular Medicine, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Structurally diverse abietane diterpenoids from the whole plants of Salvia przewalskii Maxim. With anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Tong Zhang; Shuang Xu; Xin Qiao; Guo-Shun Zhang; Qiong Zhang (Phytochemistry, 2025)

GO-SELEX-enhanced dual-recognition sensor for highly specific detection of azamethiphos - Lingjun Geng; Jingcheng Huang; Haowei Dong; Haifang Wang; Rui Xu; Zhiping Yu; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Journal of Hazardous Materials, 2025)

Addressing challenges and advancing solutions: Enhancing semi-coking wastewater treatment for a sustainable prospect - Tingting Cui; Chunhui Zhang; Bingxu Quan; Liwei Wang; Zhao Zhang; Peidong Su; Yuanhui Tang; Guifeng Zhao; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Management, 2025)

Dual-recognition strategy sensor based on GO-SELEX aptamer screening for high-specificity identification of fenthion and its major metabolites in vegetables - Lingjun Geng; Haowei Dong; Qingxia Han; Xue Huang; Jingcheng Huang; Haifang Wang; Rui Xu; Jicheng Zhao; Zhouping Wang; Shijia Wu; Ibrahim A. Darwish; Yemin Guo; et al. (Food Bioscience, 2025)

Micro-nano bubble hydrogen water irrigation improves the Cd tolerance of Ipomoea aquatica Forssk.: Rhizosphere micro-biotas modulation and oxidative stress alleviation - Xin Guo; Rui Chen; Hong Li; Guanlin Li; Qihang Zhao; Duo Wang; Jian Wang (Environmental Pollution, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Synergistic effect of canine FGF-21 combined with insulin in the treatment of canine diabetes - Wenying Sun; Yaoqun Wang; Ziran Liu; Qing Wu; Xiaochen Guo; Zhitong Li; Xinyu Li; Chunxu Shi; Rui Gao; Lin Bai; Jingming Wang; Yuhan Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

How Does Climate Change Influence the Regional Ecological–Social Risks of Harmful Dinoflagellates? A Predictive Study of China's Coastal Waters - Shangke Su; Zhaohe Luo; Jianhua Kang; Xinyuan Guo; Changyou Wang; Rui Jin; Jianguo Du; Xinqing Zheng; Kieng Soon Hii; Shifeng Fu; Wenjia Hu; Bin Chen (Global Change Biology, 2025)
Harmful dinoflagellates are widely distributed in coastal waters worldwide, posing multiple ecological and socioeconomic threats. Climate change may alter the biogeography of these species; however, few studies have linked shifts in harmful dinoflagellates' ecological distribution to their socioeconomic impacts. This study developed a framework to assess the spatiotemporal ecological–social risks posed by harmful dinoflagellates, identifying these algae as risk sources and considering mariculture and coastal populations as the primary risk receptors. China is the world's largest mariculture producer, with approximately 600 million residents living in coastal areas. Focusing on 14 key harmful dinoflagellate species in Chinese coastal waters, we evaluated ecological–social risks under present conditions and two projected climate scenarios for 2100. Our findings indicate that climate change may lead to reductions in suitable habitats for harmful dinoflagellates in tropical and subtropical regions, while habitats in higher‐latitude areas are likely to remain stable or expand. Risk area expansion is projected for four species and increased average risk intensity for three, with two species experiencing both. Nationally, total risk area is projected to remain stable, while cumulative risk intensity may decline by 16.64%. Regionally, risk intensity is expected to rise in northern provinces (up to 30.46%) and decline across most southern provinces. Importantly, we reveal a potential spatial “decoupling” of risk sources and receptors along the coast of China in the future. This decoupling demonstrates a reduced overlap between harmful dinoflagellate distributions and areas with dense mariculture or populations. Our findings suggest that, contrary to the common assumption that climate change universally exacerbates harmful algal impacts, these effects may vary across regions and species, highlighting the importance of localized adaptation strategies in risk assessment. This study provides a robust tool for understanding harmful dinoflagellate risks under climate change, thereby supporting the sustainable management of coastal ecosystems.

Decoding urban transportation: Trade-offs in mode choices using big data - Linmu Zou; Zijia Wang; Rui Guo; Lu Zhao (Transportation Research Part D: Transport and Environment, 2025)

Field test on the inclined installation performance of dynamically installed anchors - Haojie Zhang; Lizhong Wang; Hongyu Wang; Shengjie Rui; Zhen Guo (Ocean Engineering, 2025)

Efficient identification of antibiotic components in three-dimensional excitation-emission matrix fluorescence spectra via deep learning - Xu Kou; Rui Qiu; Peng Chen; Qinru Wang; Yang Chen; Hongguang Guo (Journal of Water Process Engineering, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Cement-mortar lining failure and metal release caused by electrochemical corrosion of ductile iron pipes in drinking water distribution systems - Hao Guo; Rui Wang; Menghan Jiang; Yimei Tian; Yapeng Jin; Weigao Zhao; Chenwan Wang; Jianhua Yin (Journal of Environmental Sciences, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Self-luminescent dual-ligand metal-organic framework based electrochemiluminescence probes for organophosphorus pesticides determination - Zheng Shen; Rui Xu; Guangxian Wang; Haifang Wang; Deyan Xu; JingJing Liu; Guanjie Wang; Yemin Guo; Xia Sun (Food Chemistry, 2025)

The alleviating effects of tryptophan metabolite indole-3-propionic acid on glycolipid metabolism disorders and cognitive dysfunction in obese mice - Chen Ding; Ying He; Zhitong Wang; Xiao Xiao; Yihang Zhao; Yuhao Wang; Xia Chen; Rui Guo; Yongbo She; Bin Wang; Zhigang Liu (Food Bioscience, 2025)

In vitro experiments and computer simulation techniques on the identification, screening and inhibition mechanism of xanthine oxidase (XO) inhibitory peptides from Esox lucius bone - Rui Geng; Yabo Wei; Yi Wang; Xin Guo; Xiaorong Deng; Lianfu Zhang; Jian Zhang (Food Bioscience, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Synergistic Pd-CoFe sites for efficient and selective electrooxidation of glycerol to glyceric acid coupled with H2 evolution - Jingtao Zhou; Jiu Chen; Rui Shi; Qiang Gao; Xin Zhao; Chuan-Jun Wang; Zhengxiao Guo; Edmund C.M. Tse; Fulai Liu; Yong Chen (Chemical Engineering Journal, 2025)

pH/GSH-Driven inside-out nanoreactor initiating copper(I)-precursor chelation-promoted bioorthogonal therapy - Zhexiang Wang; Xinyi Li; Rui Lv; Ruochen Guo; Qinglei Shu; Tianjin Ge; Jun Yan; Zhihao Zhao; Guanghui Wang; Jian Liu (Chemical Engineering Journal, 2025)

Tailoring porous carbon from optimized coal blends for high-performance supercapacitor electrodes - Yanli Zhu; Tao Wang; Yan Ma; Rui Sheng; Pengxu Ren; Jia Guo; Dianzeng Jia; Dongling Wu (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Long non-coding RNA HOXA11-AS inhibits apoptosis, induces proliferation, and promotes autophagy via the miR-214-3p/ATG12 axis in acute T lymphoblastic leukemia - Rui Zhang; YuanYuan Zhang; XiaoFei Li; ShaoHua Wang; Jiao Li; ShuoChun Shao; Bin Liu; WeiWei Guo; Min Shi (Journal of Molecular Histology, 2025)

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Effects of dietary Lycium barbarum polysaccharide on the growth, antioxidant, immunity response, and intestinal microbiota in Bulatmai barbel (Luciobarbus capito) - Liang Luo; Xianwei Meng; Shihui Wang; Rui Zhang; Kun Guo; Wei Xu; Wei Wang; Zhigang Zhao (Animal Feed Science and Technology, 2025)

Multiscale spatiotemporal analysis of carbon dioxide emissions in China from 2012 to 2021 based on kernel normalized difference vegetation index and nighttime light data - Rui Liu; Decheng Wang; Xirong Guo; Runcan Han; Jialiang Han; Kai Cao; Xin Pan; Juncheng Gou (Environmental Monitoring and Assessment, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Holocene coral reef carbonate REY geochemistry during the neomorphism from aragonite to calcite: A case study in the South China Sea - Wei Jiang; Yuwen Xiao; Kefu Yu; Rui Wang; Shendong Xu; Ning Guo; Tingwu Gu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A novel soil reaction model for continuous impact pile driving - Shihong Zhang; Lizhong Wang; Mengtao Xu; Shengjie Rui; Zhen Guo (Computers and Geotechnics, 2025)

Defect-repair in carbon for fast and stable potassium and sodium storage - Rui Ma; Yaxin Chen; Binyuan Zhang; Lili Ai; Changyu Leng; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2025)

Antioxidant and immunomodulator nanoengineered probiotics for synergistic therapy of inflammatory bowel disease - Pandi Peng; Rui Ding; Junru Wang; Luofeng Yu; Yuxin Guo; Pengyu Chen; Tao Feng; Peng Li (Chemical Engineering Journal, 2025)

Self-oxygenated biomimetic nano-heterojunction combats bacterial biofilm infections via near-infrared triggered ROS storms - Zhengcai Guo; Rui Zhang; Yi Li; Zhiling Chen; Tao Wang; Mingyu Wang; Xiaohong Wang; Yang Cao; Jinchun Tu; Delun Chen; Yang Wang; Qiang Wu (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

A template-free one-step synthesis of trimetallic nano-triangular structures significantly enhances the sensitivity of lateral flow immunoassays for acetamiprid detection - Jiahao Li; Baoshan He; Wenjie Ren; Ying Liang; Jinshui Wang; Rui Guo; Min Wei; Huali Jin (Analytica Chimica Acta, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Global rehabilitation research equality index across health conditions during 1990–2019: an alignment analysis between bibliographic and epidemiological data - Xin Guo; Jiakang Huo; Wanwei Dai; Tong Wang; Han Xiao; Wenjing Zhao; Xuanyu Shi; Xueheng Wang; Yang Gao; Zhi Li; Rui Zhan; Wenli Xu; et al. (Science Bulletin, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Graph-based pangenome provides insights into structural variations and genetic basis of metabolic traits in potato - Xiaoling Zhu; Rui Yang; Qiqi Liang; Yuye Yu; Tingting Wang; Li Meng; Ping Wang; Shaoyang Wang; Xianping Li; Qiongfen Yang; Huachun Guo; Qijun Sui; et al. (Molecular Plant, 2025)

Efficient degradation of norfloxacin by ZnCo2O4/halloysite composite activating peroxymonosulfate: Performance and mechanism insights - Long Zhang; Rui Li; Bohao Liu; Yubo Wang; Qingbin Guo; Junying Song; Xiongbo Dong; Li Wang; Xiaolong Hu; Dengzheng Gao (Journal of Water Process Engineering, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Variability in maternal transfer efficiency of trace elements in green turtles (Chelonia mydas) - Li Jian; Xiang Li; Xiaobo Zheng; Henyi Zhang; Minyu Fu; Rui Guo; Jichao Wang (Environmental Pollution, 2025)

Highly efficient separation of anthracene and carbazole in crude anthracene by composite extractants with low viscosity - Yuanyuan Wang; Wenhai Zhang; Danting Wang; Rui Ma; Lili Ai; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang; Hong Meng (Chemical Engineering Journal, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

Urban dynamics unveiled: A comprehensive analysis of Beijing’s subway evolution over the past decade - Linmu Zou; Zijia Wang; Rui Guo; Lu Zhao; Liang Ma (Tunnelling and Underground Space Technology, 2025)

End-to-end deep learning for pollutant prediction using street view images - Lijie Wu; Xiansheng Liu; Xun Zhang; Rui Wang; Zhihao Guo (Urban Climate, 2025)

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

A rapid and nondestructive quantitative detection method for total and organic selenium in selenium-enriched kefir grain based on hyperspectral imaging - Menghui Li; Jinyi Yang; Xing Guo; Rui Sun; Gechao Zhang; Wenhui Liu; Yuanye Liu; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Control, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Implementation and optimisation of the cdugksFoam solver on the Sunway TaihuLight supercomputer - Jie Guo; Yunlan Wang; Rui Zhang; Feifei Zhang; Tianhai Zhao; Congshan Zhuo; Sha Liu; Chengwen Zhong (Computer Physics Communications, 2025)

Insight into distribution and composition of nonhuman N-Glycans in mammalian organs via MALDI-TOF and MALDI-MSI - Rui-Rui Guo; Bram Heijs; Wen-Jun Wang; Manfred Wuhrer; Li Liu; Guinevere S.M. Lageveen-Kammeijer; Josef Voglmeir (Carbohydrate Polymers, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

PKS1 involved in anthocyanin accumulation in red-skinned pear fruit - Lei Guo; Yuting Hao; Ying Tang; Mengjia Wu; Rui Zhai; Chengquan Yang; Lingfei Xu; Zhigang Wang (Plant Cell Reports, 2025)

Subsurface drip irrigation with micro-nano bubble hydrogen water improves the salt tolerance of lettuce by regulating the antioxidant system and soil bacterial community - Jian Wang; Xin Guo; Qihang Zhao; Rui Chen; Guanlin Li; Bo Zhou; Pengfei Cheng (Applied Soil Ecology, 2025)

Assessment of the bioflocculant production and safety properties of Metabacillus hrfriensis sp. nov. based on phenotypic and whole-genome sequencing analysis - Rui Zhang; Zhigang Zhao; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Aquaculture, 2025)

Antagonistic activity of Pochonia chlamydosporia against three helminth eggs and characterization of its serine protease - Luyao Hao; Fengmiao Zhao; Yuan Guo; Yuan Ma; Zhengyi Li; Wen Wang; Hongliang Luo; Rui Wang (Veterinary Parasitology, 2025)

Parametric investigation of suction actuators on the tunnel wall for alleviating pressure interactions in high-speed maglev train/tunnel system - Zheng-Wei Chen; Zhan-Hao Guo; Yi-Qing Ni; Zi-Jian Guo; Tian-Tian Wang; En-Ze Rui; Guang-Zhi Zeng (Tunnelling and Underground Space Technology, 2025)

Significant increases in nitrous oxide emissions under simulated extreme rainfall events and straw amendments from agricultural soil - Xiaogang Li; Rui Wang; Yanling Du; Hui Han; Shengli Guo; Xiaotong Song; Xiaotang Ju (Soil and Tillage Research, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Evaluating soil water and nitrogen transport, nitrate leaching and soil nitrogen concentration uniformity under sprinkler irrigation and fertigation using numerical simulation - Rui Chen; Xiaofang Chen; Hong Li; Jian Wang; Xin Guo (Journal of Hydrology, 2025)

Species-specific accumulation of microplastics in different bird species from South China: A comprehensive analysis - Ying Zeng; Junjie Cai; Yujing Zhu; Jichao Wang; Rui Guo; Li Jian; Xiaobo Zheng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Borides and sulfide quantum dots co-enhanced the electrochemical property of metal organic framework/Ni3S2 composites for high-performance supercapacitors - Shuai Wu; Debin Cai; Hong Wang; Rui Zhou; Li Guo; Yanzhong Wang (Fuel, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

Preparation strategy of molecularly imprinted polymers adsorbent based on multifunctional carrier for precise identification and enrichment of fenthion - Lingjun Geng; Jingjing Liu; Jingcheng Huang; Haifang Wang; Peisen Li; Rui Xu; Chengqiang Li; Haowei Dong; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Novel time-resolved fluorescent-based multiplex immunochromatography test strip for simultaneous detection of pesticides in vegetables - Zhengtao Li; Haowei Dong; Haifang Wang; Donghan Li; Shuxian Zhou; Shengxi Zhai; Jingcheng Huang; Rui Xu; Wenping Zhao; Mohamed Bedair M. Ahmed; Gili Bisker; Xia Sun; et al. (Food Chemistry, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Effect of carrageenan on stability and 3D printing performance of high internal phase pickering emulsion stabilized by soy protein isolate aggregates under neutral condition - Rui Li; Xiuqin Guo; Pengfei Liu; Yuanyuan Li; Si Qiu; Yuntao Wang (Carbohydrate Polymers, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Thirty-year dryland crop rotation improves soil multifunctionality and shifts soil fungal community - Ying Wang; Hongfei Ji; Yan Chen; Rui Wang; Shengli Guo (Plant and Soil, 2025)

Differential responses of soil CO2 dynamics along soil depth to rainfall patterns in the Chinese Loess Plateau - Xiao Yang; Rui Wang; Mengdi Yang; Quanfeng Liu; Wenju Zhang; Shengli Guo (Agriculture, Ecosystems & Environment, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

Heat-resistant boron Carbonitride with nitrogen-vacancies and oxygen-doping for efficient tetracycline removal: Adsorption characteristics, mechanism and regeneration - Xu-Dong Miao; Rui-Xiang Zhang; Wen-Tao Li; Qian Wang; Yu-Han Cai; Yong Guo; Ai-Min Li (Journal of Water Process Engineering, 2025)

Corporate innovation's impact on the cost of equity: Evidence from Chinese listed companies - Shixin Zheng; Xuefeng Wang; Yongji Zhang; Rui Guo; Hongshu Chen (Journal of Cleaner Production, 2025)

U-shaped relationship between environmental regulation and the digital transformation of the Chinese coal industry: Mechanism and moderating effects - Pu-hao Guo; Xiang-qian Wang; Xiang-rui Meng (Journal of Environmental Management, 2025)

Aged garlic oligosaccharides modulate host metabolism and gut microbiota to alleviate high-fat and high-cholesterol diet-induced atherosclerosis in ApoE−/− mice - Xiaomin Wang; Jianglu Cui; Ziyao Gu; Lili Guo; Rui Liu; Yu Guo; Nan Qin; Yukun Yang (Food Chemistry, 2025)

Fabrication of the ferritin-mannoprotein shell-core heteroprotein complex for stabilization of bioactive molecules - Xinmei Sha; Runxuan Chen; Yichen Li; Tianyang Wang; Ku Li; Hui Guo; Yuyu Zhang; Rui Yang (Food Hydrocolloids, 2025)

Effects of water immersion on immune, intestinal flora and metabolome of Chinese mitten crab (Eriocheir sinensis) after air exposure - Xiangyi Deng; Zhiqiang Li; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Guo Qiao; Yuhong Yang; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Regulation of oxygen vacancy by in-situ piezoelectric synthesized BiVO4 to induce spin polarization for boosting the piezo-photocatalytic activity - Ying Cheng; Tao Yu; Xuefei Lei; Biao Wang; Wenning Mu; Xuanwen Liu; Rui Guo (Chemical Engineering Journal, 2025)

Towards resilient communities: Evaluating the nonlinear impact of the built environment on COVID-19 transmission risk in residential areas - Weiqi Guo; Jingwei Wang; Xiaoyu Liu; Zhenyu Pan; Rui Zhuang; Chunying Li; Haida Tang (Building and Environment, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

Effect of clayey sediment compression on fluoride enrichment in the Quaternary groundwater system of Cangzhou Plain, China - Rui Liu; Haipeng Guo; Juan Chen; Haigang Wang; Xisheng Zang; Guijie Wang; Yunlong Wang; Juyan Zhu (Journal of Hazardous Materials, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Occurrence and distribution of phytic acid and its degradation products in soybeans in China: Analytical challenges - Jiayue Chen; Zhenjun Liu; Xinru Cui; Rui Yang; Xinru Guo; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Black phosphorus-loaded anisotropic nanofiber sponges for random skin flaps regeneration - Sizhe Song; Jiahui Guo; Bin Kong; Rui Liu; Jinglin Wang; Ling Lu; Yuanjin Zhao (Chemical Engineering Journal, 2024)

Deciphering the nonlinear and synergistic role of building energy variables in shaping carbon emissions: A LightGBM- SHAP framework in office buildings - Congyue Zhou; Zhu Wang; Xuanli Wang; Rui Guo; Zhao Zhang; Xingwei Xiang; Yiqun Wu (Building and Environment, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

SLC15A3 is transcriptionally regulated by HIF1α and p65 to worsen neuroinflammation in experimental ischemic stroke - Shan Yu; Jinghui Yang; Rui Zhang; Qian Guo; Lu Wang (Molecular Neurobiology, 2024)

Yam (Rhizoma Dioscoreae) polysaccharide affects growth performance, immunity, and intestinal microbial community in Bulatmai barbel (LucioBarbus capito) - Liang Luo; Xianwei Meng; Shihui Wang; Rui Zhang; Kun Guo; Gaochao Wang; Wei Wang; Zhigang Zhao (Animal Feed Science and Technology, 2024)

ZC3H13 promotes autophagy in bladder cancer through m6A methylation modification of PJA2 and ubiquitination of KSR1 - Beibei Liu; Mengjie Chen; Yujie Liang; Zhijie Mei; Wei Sun; Wuyue Gao; Tiantian Zhang; Rui Wang; Yuanyuan Guo (Human Cell, 2024)

Ferritinophagy is involved in hexavalent chromium-induced ferroptosis in Sertoli cells - Ruijian Zhuge; Le Zhang; Qian Xue; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Chunyang Meng; Rifeng Lu; Fei Yin; Li Guo (Toxicology and Applied Pharmacology, 2024)

Hexavalent chromium reduces testosterone levels by impairing lipophagy and disrupting lipid metabolism homeostasis: Based on a metabolomic analysis - Qian Xue; Le Zhang; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Shidi Gao; Xin Fang; Chunyang Meng; Rifeng Lu; Li Guo (Toxicology, 2024)

Comprehensive compositional analysis of liquid organic product prepared by industrialized hydrothermal cracking of biomass waste and its potential application as fertilizer - Rui Xia; Jue Wang; Xiao-xiao Yang; Qing-hai Li; Hui Zhou; Hui Sun; Yan-guo Zhang (Science of The Total Environment, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Photo-induced BiVO4 to produce P25-like structure for enhancing piezo-photocatalytic activity - Ying Cheng; Zhiyuan Ni; Wenliang Wang; Xuefei Lei; Biao Wang; Xuanwen Liu; Rui Guo (Journal of Water Process Engineering, 2024)

Effects of 12-year cropping systems and tillage practices on crop yield and carbon trade-off in dryland Loess Plateau - Xingyu Guo; Hao Wang; Naeem Ahmad; Rui Wang; Xiaoli Wang; Jun Li (Field Crops Research, 2024)

Assessment of seabed trench formation based on marine sediment properties and chain-bar penetration tests - Shengjie Rui; Hans Petter Jostad; Zefeng Zhou; Lizhong Wang; Svein Sævik; Yufei Wang; Zhen Guo (Engineering Geology, 2024)

Manipulating surface reconstruction and lattice oxygen mechanism of nickel (oxy)hydroxide by defect engineering for industrial electrocatalytic water oxidation - Xiangling Wang; Zhimin Li; Yu Tang; Zhengfu Zhang; Chengping Li; Rui Bao; Guo Chen; Jinsong Wang (Chemical Engineering Journal, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Association of the COL4A2 Gene Polymorphisms with Primary Intracerebral Hemorrhage Risk and Outcome in Chinese Han Population - Huan Wang; Yuyi Zhu; Lukai Zheng; Mingxi Chen; Zilong Hao; Rui Guo; Ling Feng; Deren Wang (Molecular Neurobiology, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

Flow Field Analysis and Development of a Prediction Model Based on Deep Learning - Yingjie Yu; Xiufeng Zhang; Lucai Wang; Rui Tian; Xiaobin Qian; Dongdong Guo; Yanwei Liu (Journal of Marine Science and Engineering, 2024)
The velocity of ocean currents significantly affects the trajectory prediction of ocean drifters and the safe navigation of intelligent vessels. Currently, most ocean current predictions focus on time-based forecasts at specific fixed points. In this study, deep learning based on the flow field prediction model (CNNs–MHA–BiLSTMs) is proposed, which predicts the changes in ocean currents by learning from historical flow fields. Unlike conventional models that focus on single-point current velocity data, the CNNs–MHA–BiLSTMs model focuses on the ocean surface current information within a specific area. The CNNs–MHA–BiLSTMs model integrates multiple convolutional neural networks (CNNs) in parallel, multi-head attention (MHA), and bidirectional long short-term memory networks (BiLSTMs). The model demonstrated exceptional modelling capabilities in handling spatiotemporal features. The proposed model was validated by comparing its predictions with those predicted by the MIKE21 flow model of the ocean area within proximity to Dalian Port (which used a commercial numerical model), as well as those predicted by other deep learning algorithms. The results showed that the model offers significant advantages and efficiency in simulating and predicting ocean surface currents. Moreover, the accuracy of regional flow field prediction improved with an increase in the number of sampling points used for training. The proposed CNNs–MHA–BiLSTMs model can provide theoretical support for maritime search and rescue, the control or path planning of Unmanned Surface Vehicles (USVs), as well as protecting offshore structures in the future.

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Antimicrobial blue light inactivation of Pseudomonas aeruginosa: Unraveling the multifaceted impact of wavelength, growth stage, and medium composition - Yucheng Wang; Xue Li; Hongtong Chen; Xinyi Yang; Lei Guo; Rui Ju; Tianhong Dai; Guoqing Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

A combined experimental and theoretical study on the mechanism of catalytic oxidation of lignite to carboxylic acids by iron - Jiao-Xuan Bai; Cong Xu; Jie-Ping Wang; Rui Guo; Wei-Ze Wu; Ting Lu; Guang-Yue Li; Ying-Hua Liang (Fuel, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Hybrid plasma catalysis-thermal system for non-oxidative coupling of methane to ethylene and hydrogen - Rui Liu; Eduardo Morais; Dongxing Li; Pengfei Liu; Qian Chen; Shangkun Li; Li Wang; Xiaoxia Gao; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2024)

Highly dispersed ternary metal FeZnCe with nitrogen/oxygen co-doped carbon materials for efficient oxygen electroreduction - Fuxian Zheng; Yajie Guo; Ting Wang; Xianghui Meng; Konggang Qu; Lei Wang; Rui Li; Zongge Li; Wenjun Kang; Haibo Li (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Evolutionary dynamics of cooperation coupled with ecological feedback compensation - Zi-Xuan Guo; Tian-Jiao Feng; Yi Tao; Rui-Wu Wang; Xiu-Deng Zheng (BioSystems, 2024)

Advances in the Differentiation of hiPSCs into Cerebellar Neuronal Cells - Yingxin Wang; Wenzhu Liu; Yichang Jiao; Yitong Yang; Didi Shan; Xinbo Ji; Rui Zhang; Zexin Zhan; Yao Tang; Dandan Guo; Chuanzhu Yan; Fuchen Liu (Stem Cell Reviews and Reports, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

A study on the monitoring of landslide deformation disasters in Wenxian County, Longnan City based on different time-series InSAR techniques - Jinlong Zhang; Rui Yang; Yuan Qi; Hui Zhang; Juan Zhang; Qianhong Guo; Chao Ma; Hongwei Wang (Natural Hazards, 2024)

Earthworms and Arbuscular Mycorrhizal Fungi Alleviated Salt Stress in Maize Seedlings by Regulating the Root Endodermis Diffusion Barrier - Binglei wang; Chong Wang; Lei Zhao; Xuelian Liu; Rui Xue; Jia Cao; Siping Li; Mengyao Guo; Huiying Huang (Journal of Plant Growth Regulation, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Semi-liquid metal-based highly permeable and adhesive electronic skin inspired by spider web - Rui Guo; Xiaoqing Li; Yingtong Zhou; Yuqi Zhang; Chengjie Jiang; Yang Yu; Qingting Tan; Wenbo Ding; Hongzhang Wang (Science Bulletin, 2024)

Rare oxoisoaporphine alkaloids from Menispermum dauricum with potential anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Xiao-Juan Cao; Xiao-Juan Yao; Xin Qiao; Ya-Tian Meng; Tong Zhang; Qiong Zhang (Phytochemistry, 2024)

Antiviral C-geranylated flavonoids from Artocarpus communis - Rui-Li Huang; Wei Tang; Chaoqun Wang; Cong Yan; Yun Hu; Hai-Xia Yang; Hai-Yang Xiang; Xiao-Jun Huang; Li-Jun Hu; Wen-Cai Ye; Jian-Guo Song; Ying Wang (Phytochemistry, 2024)

Insights into the photoreactivity mechanisms of micro-sized rubber particles with different structure: The crucial role of reactive oxygen species and released dissolved organic matter - Rui Ding; Zhuozhi Ouyang; Pingshu Dong; Tianyuan Su; Jingzhen Wang; Xuetao Guo (Journal of Hazardous Materials, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

Photochromic ionogel with a wide temperature range and fatigue resistance for high-resolution rewritable information record - Jingyue Zhang; Mengru Guo; Yuanteng Su; Wenxia Wu; Shicheng Wang; Rui Yang; Chao Xu; Hongzong Yin; Jiaheng Xu; Xiaolin Wang (Chemical Engineering Journal, 2024)

Genome-wide association study and selective sweep analysis uncover candidate genes controlling curd branch length in cauliflower - Yingxia Yang; Yutong Guo; Jing Wang; Wenjuan Cheng; Mingjie Lyu; Qian Wang; Jianjin Wu; Mingyan Hua; Weihua Zhang; Deling Sun; Xianhong Ge; Xingwei Yao; et al. (Theoretical and Applied Genetics, 2024)

How territorial function determines CO2 emissions in China: An approach of spatial dimension - Jie Fan; Zheng Wang; Daojing Zhou; Rui Guo; Dong Chen; Baoyin Liu; Hanchu Liu; Qin Qiao; Jianxiong Wu (Journal of Geographical Sciences, 2024)

Correction to: Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

A lightweight and efficient hollow sunken carbon@MnO2/reduced graphene oxide composite for high-performance electromagnetic wave absorption - Yuxia Shi; Baoquan Liang; Hong Gao; Rui Zhao; Yingzan Zhuang; Qin Guo; Xianhan Shao; Hankun Wang; Mingliang Ma; Tingxi Li; Yong Ma (Chemical Engineering Journal, 2024)

Oxygen-driven closing pore formation in coal-based hard carbon for low-voltage rapid sodium storage - Rui Ma; Yaxin Chen; Qian Li; Binyuan Zhang; Feifei Chen; Changyu Leng; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2024)

Genetic affinity of cave burial and Hmong-Mien populations in Guangxi inferred from ancient genomes - Jianxin Guo; Haifeng He; Guangmao Xie; Le Tao; Xi Mai; Kongyang Zhu; Qiusheng Qin; Xiaomin Yang; Ying Xie; Rui Wang; Hao Ma; Jing Zhao; et al. (Archaeological and Anthropological Sciences, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Understanding secondary particles in a regional site of Yangtze River Delta: Insights from mass spectrometric measurement - Wenfei Zhu; Jialin Shi; Hui Wang; Ying Yu; Rui Tan; Ruizhe Shen; Jun Chen; Shengrong Lou; Min Hu; Song Guo (Science of The Total Environment, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Electrochemiluminescence detection of diazinon in vegetables based on the synergistic interaction of WO3-x dots with Au@SiO2 nanocapsules - Wenzheng Liu; Haifang Wang; Peisen Li; Chengqiang Li; Donghan Li; Zhenying He; Yuhao Zhang; Jingcheng Huang; Jin Hua; Rui Xu; Lianming Xia; Yemin Guo; et al. (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Untargeted LC–MS metabolomics reveals the metabolic responses in the Eriocheir sinensis gills exposed to salinity and alkalinity stress - Shihui Wang; Yingying Song; Liang Luo; Rui Zhang; Kun Guo; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Editorial: Frontiers in marine sciences, social sciences and engineering research related to marine (renewable) energy development - Shengjie Rui; Zhen Guo; Zefeng Zhou; Zhenkui Wang; Guanqiong Ye; Dongfang Ma (Frontiers in Marine Science, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Coupling control of organic and inorganic rock components on porosity and pore structure of lacustrine shale with medium maturity: A case study of the Qingshankou Formation in the southern Songliao Basin - Dianshi Xiao; Lehua Zheng; Jilin Xing; Min Wang; Rui Wang; Xiaodie Guan; Xueyi Guo (Marine and Petroleum Geology, 2024)

Responses of rainfall partitioning to water conditions in Chinese forests - Qi Wu; Rui Yang; Hui Zeng; Xiang Wang; Guo Chen (Journal of Hydrology, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Synthesis, characterization, and environmental evaluation of Fe-PCN-134: A mixed-linker metalloporphyrin MOF for the degradation of atrazine via visible photo-Fenton reaction - Meng Yu; Yinmin Wang; Yingjian Ma; Zhe Sun; Li Ma; Shouhe Pan; Rui Zhao; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2024)

Effect of nano zero-valent iron on the anaerobic digestion of food waste: Performance and mechanism - Ruonan Wang; Naif Abdullah Al-Dhabi; Yufeng Jiang; Xiaofeng Dai; Rui Li; Wangwang Tang; Rongbo Guo; Shanfei Fu (Fuel, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Stretchable ionogels: Recent advances in design, toughening mechanisms, material properties and wearable devices applications - Caiyue Huang; Xiaohua Jia; Ding Wang; Xisheng Sun; Qi Liang; Rui Tian; Liyuan Guo; Jin Yang; Haojie Song (Chemical Engineering Journal, 2024)

Electrochemically assisted preparation of graphitic carbon nitride nanosheet membranes for efficient water purification - Yisa Zhou; Ya Zhang; Jian Xue; Rui Wang; Jiale Dong; Zongjie Yin; Chen Guo; Haihui Wang (Chemical Engineering Journal, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Artemisia argyi H. Lév. & Vaniot: a comprehensive review on traditional uses, phytochemistry, and pharmacological activities - Wen-Jun Wei; Tao Guo; Gui-Min Xue; Rui Ma; Yuefei Wang; Zhe-Sheng Chen (Phytochemistry Reviews, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Curcumol: a review of its pharmacology, pharmacokinetics, drug delivery systems, structure–activity relationships, and potential applications - Sicheng Zhai; Rui Wang; Jingyuan Wang; Xiangdong Xu; Le Niu; Min Guo; Yongling Zhang; Yajun Shi; Xuexue Tang (Inflammopharmacology, 2024)

Air permeability variation of compacted loess: effects of soil basic properties and dry-wet cycles - Shi-Feng Lu; Xiao-Pei Guo; Xing-Rui Wang; Zi-Jing Han; Ling Xu; Xiao-Lin Huang; Lu Zuo (Bulletin of Engineering Geology and the Environment, 2024)

Intestinal carcinogenicity screening of environmental pollutants using organoid-based cell transformation assay - Ziwei Wang; Shen Chen; Yuzhi Guo; Rui Zhang; Qi Zhang; Xinhang Jiang; Miao Li; Yue Jiang; Lizhu Ye; Xiaoyu Guo; Chuang Li; Guangtong Zhang; et al. (Archives of Toxicology, 2024)

Unveiling of dietary and gut-microbiota derived B vitamins: Metabolism patterns and their synergistic functions in gut-brain homeostasis - Qi Zhan; Rui Wang; Kiran Thakur; Jing-Yu Feng; Yun-Yang Zhu; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2024)

Establishment, characterization and application of Largemouth bronze gudgeon (Coreius guichenoti) fin and skin cell lines in disease resistance - Qi Zhang; Zhihong Gong; Rui Shi; Yuhong Shi; Chenfei Guo; Xiaolin Liao; Hua Tian; Na Wang (Aquaculture, 2024)

Association between air pollution and male sexual function: A nationwide observational study in China - Ziyuan Shen; Feng Zhang; Zihan Guo; Rui Qu; Yiqiu Wei; Jingxuan Wang; Weiqian Zhang; Xing Xing; Yan Zhang; Jue Liu; Dongdong Tang (Journal of Hazardous Materials, 2024)

Forest fire susceptibility assessment under small sample scenario: A semi-supervised learning approach using transductive support vector machine - Tianwu Ma; Gang Wang; Rui Guo; Liang Chen; Junfei Ma (Journal of Environmental Management, 2024)

Effects of ultrasonic treatment on the texture quality of aged rice flour - Yubao Guo; Rui Song; Shimin Zhu; Xinyu Liu; Xinyu Wang (Journal of Cereal Science, 2024)

Experimental study and model optimization of thermodynamic performance of a single screw water vapor compressor - Huafu Zhang; Zhentao Zhang; Lige Tong; Junling Yang; Yanan Li; Li Wang; Xia Guo; Rui Tian; Mingxin He; Chongguang Gao (International Journal of Refrigeration, 2024)

Temperature driven real-time weakening and strengthening mechanisms of unconfined granite - Fei Wang; Rui Pang; Heinz Konietzky; Ke Hu; Ben-Guo He; De-Hao Meng; Mohamed Ismael (Geothermics, 2024)

Enhanced efficiency nitrogen fertilizers (EENFs) can reduce nitrous oxide emissions and maintain high grain yields in a rain-fed spring maize cropping system - Yanling Du; Yuan Lu; Shengli Guo; Rui Wang; Xiaotong Song; Xiaotang Ju (Field Crops Research, 2024)

Effects of pretension loads on bending behaviors of CFRP tendons - Zhen Wang; Rui Guo; Bin Hong; Guijun Xian; Meiyin Xin; Shengde Huang; Haijuan Shen (Engineering Structures, 2024)

Exploiting genomic tools for genetic dissection and improving the resistance to Fusarium stalk rot in tropical maize - Junqiao Song; Yubo Liu; Rui Guo; Angela Pacheco; Carlos Muñoz-Zavala; Wei Song; Hui Wang; Shiliang Cao; Guanghui Hu; Hongjian Zheng; Thanda Dhliwayo; Felix San Vicente; et al. (Theoretical and Applied Genetics, 2024)

Impact of remaining roots on soil nematode communities in an aboveground plant functional group removal experiment - Yong Zheng; Ligai Huang; Xue Jiang; Rui Guo; Wenjie Wan; Luping Ye; Tibor A. Drost; Xianhui Zhou; Hui Guo; Juan Zuo; Peng Wang (Plant and Soil, 2024)

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Cycads: A comprehensive review of its botany, traditional uses, phytochemistry, pharmacology and toxicology - Qinyun Du; Nan Xing; Sa Guo; Rui Li; Xianli Meng; Shaohui Wang (Phytochemistry, 2024)

Carbazomycins I and J, two novel carbazole alkaloids isolated from Saccharopolyspora phattalungensis - Wen Wang; Er Juan Zhao; Ting Peng; Zhang Yuan Yan; Zhi Kai Guo; Rui Hua Jiao (Phytochemistry Letters, 2024)

Arbuscular mycorrhizal fungi reduce ammonia emissions under different land-use types in agro-pastoral areas - Huaisong WANG; Rui GUO; Yibo TIAN; Nan CUI; Xinxin WANG; Lei WANG; Zhongbao YANG; Shuying LI; Jixun GUO; Lianxuan SHI; Tao ZHANG (Pedosphere, 2024)

Hollow α-Bi2O3/TiO2 nanotube arrays hierarchical heterojunction with strong interface interaction for efficient photocatalytic ciprofloxacin degradation - Bingrui Ma; Yuxin Zha; Rui Xu; Jincheng Li; Yajing Guo; Jie Liu; Songxue Wang; Boyin Yan; Yunlong Lan; Baoxiu Zhao; Haijiao Xie (Journal of Water Process Engineering, 2024)

Association between ambient PM1 and the prevalence of chronic kidney disease in China: A nationwide study - Rui Chen; Chao Yang; Yuming Guo; Gongbo Chen; Shanshan Li; Pengfei Li; Jinwei Wang; Ruogu Meng; Huai-yu Wang; Suyuan Peng; Xiaoyu Sun; Fulin Wang; et al. (Journal of Hazardous Materials, 2024)

Effects of belt trusses on drift control of frame-core tube structures - Wen-Bo Wang; Hong-Song Hu; Rui-Tao Wang; Yi-Chao Gao; Zi-Xiong Guo (Engineering Structures, 2024)

Molten salt etching synthesis of Ti3C2Tx/Ni composites for highly efficient capacitive deionization - Wen Xi; Tianzhuo Guo; Zeren Xie; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Desalination, 2024)

Seven mechanisms of oxygen evolution reaction proposed recently: A mini review - Zihang Feng; Chuanlin Dai; Peng Shi; Xuefei Lei; Rui Guo; Biao Wang; Xuanwen Liu; Junhua You (Chemical Engineering Journal, 2024)

Field implementation to resist coastal erosion of sandy slope by eco-friendly methods - Yujie Li; Zhen Guo; Lizhong Wang; Yongqiang Zhu; Shengjie Rui (Coastal Engineering, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Metabolomics reveals how spinach plants reprogram metabolites to cope with intense stress responses induced by photoaged polystyrene nanoplastics (PSNPs) - Daofen Huang; Ling Ding; Shuhua Wang; Rui Ding; Xinran Qiu; Jianlong Li; Zhengdong Hua; Shasha Liu; Renren Wu; Xujun Liang; Xuetao Guo (Journal of Hazardous Materials, 2024)

Occurrence, transmission and risks assessment of pathogens in aquatic environments accessible to humans - Yiyi Su; Rui Gao; Fang Huang; Bin Liang; Jianhua Guo; Lu Fan; Aijie Wang; Shu-Hong Gao (Journal of Environmental Management, 2024)

Inactivation activity and mechanism of pulsed light against Alicyclobacillus acidoterrestris vegetative cells and spores in concentrated apple juice - Rui Cai; Yali Ma; Zhouli Wang; Yahong Yuan; Hong Guo; Qinglin Sheng; Tianli Yue (International Journal of Food Microbiology, 2024)

Myofibril degradation and structural changes in myofibrillar proteins of porcine longissimus muscles during frozen storage - Rui Wang; Fang Guo; Jianying Zhao; Caiping Feng (Food Chemistry, 2024)

Effect of konjac glucomannan with different degrees of deacetylation on the gel behavior of transglutaminase induced soybean protein isolate emulsion gels - Yuntao Wang; Hui Zhang; Qing Liang; Xiuqin Guo; Zijian Niu; Si Qiu; Wei Xu; Rui Li (Food Hydrocolloids, 2024)

Chlorogenic acid improves common carp (Cyprinus carpio) liver and intestinal health through Keap-1/Nrf2 and NF-κB signaling pathways: Growth performance, immune response and antioxidant capacity - Guo-Jun Shang; Si-ying Liu; Rui Zhu; Deng-Lai Li; Si-Tong Meng; Yin-tao Wang; Li-Fang Wu (Fish & Shellfish Immunology, 2024)

Optimizing maize productivity: A sustainable approach integrating straw derivatives and film mulching in rainfed agriculture - Rui Qian; Zijun Ma; Yunyun Yang; Ru Guo; Fei Han; Jinjin Wang; Xiaoling Wang; Baoping Sun; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Field Crops Research, 2024)

Spatial distribution and risk assessment of pyrethroid insecticides in surface waters of East China Sea estuaries - Rui Wang; Feng Wang; Yintao Lu; Shengwei Zhang; Minghong Cai; Dongdong Guo; Hongyuan Zheng (Environmental Pollution, 2024)

Removing refractory organic substances from landfill leachate using a nanofiltration membrane bioreactor: Performance and mechanisms - Chu Zhou; Na Li; Wenbin Guo; Rui Wang; Yaohua Yan; Senlin Shao (Chemical Engineering Journal, 2024)

Iodide-based glass with combination of high transparency and conductivity: A novel promising candidate for transparent microwave absorption and radar stealth - Chen Guo; Chao Chen; Rui Wan; Liqing Yang; Yongmao Guan; Pengfei Wang (Chemical Engineering Journal, 2024)

Covalent-Metal organic Frameworks: Preparation and applications - Zhaobo Wang; Chen Wang; Qiming Hu; Xuefei Lei; Rui Guo; Junhua You; Ye Tian; Fan Yang; Meili Lv (Chemical Engineering Journal, 2024)

Differentiation of prokaryotic community composition in suspended sediment size-fractionation in a small loess watershed - Tongtong Li; Wei Zhang; Lin Yang; Shengli Guo; Rui Wang (CATENA, 2024)

Serum Uric Acid Levels and Outcome of Acute Ischemic Stroke: a Dose–Response Meta-analysis - Peng Zhang; Rui Wang; Yang Qu; Zhen-Ni Guo; Qing Zhen; Yi Yang (Molecular Neurobiology, 2024)

Effects of Fractionation Methods on Soil Aggregate Microbial Community Composition: Settling vs. Wet Sieving - Xin Gao; Rui Wang; Yaxian Hu; Weijia Li; Lanlan Du; Shengli Guo; Shengjun Wu; Ping Huang (Journal of Soil Science and Plant Nutrition, 2024)

Warming Tends to Promote Nitrogen Conservation but Stimulate N2O Emissions in Mangrove Sediments - Ning Zhang; Rui Guo; Feifei Wang; Zetao Dai; Yasong Li; Wenzhi Cao (Ecosystems, 2024)

Soil nutrients drive changes in the structure and functions of soil bacterial communities in a restored forest soil chronosequence - Rui Guo; Yiyue Chen; Meiren Xiang; Shengchang Yang; Feifei Wang; Wenzhi Cao; Hui Yue; Shaoyun Peng (Applied Soil Ecology, 2024)

The Effect of Artificial Substrate and Carbon Source Addition on Bacterial Diversity and Community Composition in Water in a Pond Polyculture System - Kun Guo; Mumin Shi; Xiaoli Huang; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Guoliang Ruan; Zhigang Zhao (Fishes, 2024)
The use of artificial substrates and biofloc technology can favor fish culture and improve water quality. The aim of this study was to evaluate whether artificial substrates and carbon source additions modify the microbial activity of water bodies. The diversity and structure of microflora in the water after adding artificial substrates and carbon sources to the ponds were analyzed using high-throughput sequencing based on the V3-V4 region of 16S rRNA genes. The results showed that there was no difference in the richness and diversity of intestinal microflora between the control and experimental groups. Principal coordinate analysis (PCoA) and nonmetric multidimensional scaling (NMDS) showed that artificial substrate and carbon source addition changed the structure of the microflora. The results of a linear discriminant analysis (LDA) effect size (LefSe) indicated 11 biomarkers in the EGˍst group. Spearman correlation heatmap analysis showed that environmental factors affected the bacterial communities, and the results of a redundancy analysis indicated that chemical oxygen demand was a critical factor in controlling the bacterial communities in the water. These results provide an understanding of the effect of artificial substrate and carbon source addition on bacterial diversity and community composition in water.

Dynamic spillover effects between EU economic sanctions against Russia, oil prices, and share prices of energy companies in third countries: evidence from China and the USA - Ming Li; Zaixu Zhang; Xiaoyu Wang; Rui Guo (Environmental Science and Pollution Research, 2024)

Hybrid organic frameworks: Synthesis strategies and applications in photocatalytic wastewater treatment - A review - Zhaobo Wang; Hongxin Wang; Peng Shi; Jiangyuan Qiu; Rui Guo; Junhua You; Hangzhou Zhang (Chemosphere, 2024)

Spatial distribution characteristics of perfluoroalkyl substances in bulk and grain size fractionated sediments in Shenzhen Bay - Haoshuai Li; Zimin Wang; Yang Zhou; Cui Shi; Huayang Gan; Fang Chen; Lei Xing; Danxu Guo; Longhai Zhu; Nan Wang; Shuhong Fang; Rui Bao (Marine Pollution Bulletin, 2024)

Neonicotinoids: Advances in hazards of residues, screening of aptamers and design of aptasensors - Jingcheng Huang; Haifang Wang; Haowei Dong; Mengyue Liu; Lingjun Geng; Jiashuai Sun; Zhen Guo; Rui Xu; Giovanna Marrazza; Xia Sun; Yemin Guo (Trends in Food Science & Technology, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

Life cycle analysis of common landfill final cover systems focusing on carbon neutrality - Charles Wang Wai Ng; Hongqi Chen; Haowen Guo; Rui Chen; Qiang Xue (Science of The Total Environment, 2024)

Using machine learning to predict selenium and cadmium contents in rice grains from black shale-distributed farmland area - Rucan Guo; Rui Ren; Lingxiao Wang; Qian Zhi; Tao Yu; Qingye Hou; Zhongfang Yang (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Compartmentalization transformation of Fe2+, Mn2+ and NH4+ in groundwater: A comparative research containing experimental medium and functional genera profiling derived from experiment data - Li Meng; Jian Shi; Shida Zheng; Xueru-Guo; Jinsheng Wang; Yuanzheng Zhai; Yanguo Teng; Rui Zuo (Journal of Water Process Engineering, 2024)

How carbon trading influences manufacturing/remanufacturing? A coordination mechanism design based on outsourced remanufacturing - Jingyuan Guo; Rui Wu; Wei Wang; Weidi Zhu (Journal of Cleaner Production, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Carbon trade-off and energy budgeting under conventional and conservation tillage in a rice-wheat double cropping system - Naeem Ahmad; Ahmad Latif Virk; Abdul-Sattar Nizami; Rattan Lal; Scott X. Chang; Muhammad Bilal Hafeez; Xingyu Guo; Rui Wang; Xiaoli Wang; Hafiz Muhammad Waleed Iqbal; Gadah Albasher; Jun Li (Journal of Environmental Management, 2024)

Evolution of carbon deposits during ethylene aromatization over Zn/ZSM-5 - Rui Geng; Yacong Liu; Yanxia Guo; Mei Dong; Sen Wang; Weibin Fan; Jianguo Wang; Zhangfeng Qin (Fuel, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Boosting ion diffusion kinetics of Fe2O3/MoC@NG via heterointerface engineering and pseudocapacitance behavior: An alternative high-rate anode for high‐capacity lithium dual-ion batteries - Juan Ding; Yudai Huang; Wenhua Cheng; Rui Sheng; Zhenjie Liu; Xingchao Wang; Yong Guo; Jiulin Wang; Dianzeng Jia; Xincun Tang; Lei Wang (Chemical Engineering Journal, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

Distinct variabilities of soil abundant and rare bacteria relate differently to carbon cycling functionality in eroded ecosystems - Lanlan Du; Shengli Guo; Rui Wang; Yanqing Guo; Yaxian Hu; Lin Yang; Weijia Li (CATENA, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

A global meta‐analysis of yield‐scaled N 2 O emissions and its mitigation efforts for maize, wheat, and rice - Zhisheng Yao; Haojie Guo; Yan Wang; Yang Zhan; Tianli Zhang; Rui Wang; Xunhua Zheng; Klaus Butterbach‐Bahl (Global Change Biology, 2024)
Maintaining or even increasing crop yields while reducing nitrous oxide (N 2 O) emissions is necessary to reconcile food security and climate change, while the metric of yield‐scaled N 2 O emission (i.e., N 2 O emissions per unit of crop yield) is at present poorly understood. Here we conducted a global meta‐analysis with more than 6000 observations to explore the variation patterns and controlling factors of yield‐scaled N 2 O emissions for maize, wheat and rice and associated potential mitigation options. Our results showed that the average yield‐scaled N 2 O emissions across all available data followed the order wheat (322 g N Mg −1 , with the 95% confidence interval [CI]: 301–346) > maize (211 g N Mg −1 , CI: 198–225) > rice (153 g N Mg −1 , CI: 144–163). Yield‐scaled N 2 O emissions for individual crops were generally higher in tropical or subtropical zones than in temperate zones, and also showed a trend towards lower intensities from low to high latitudes. This global variation was better explained by climatic and edaphic factors than by N fertilizer management, while their combined effect predicted more than 70% of the variance. Furthermore, our analysis showed a significant decrease in yield‐scaled N 2 O emissions with increasing N use efficiency or in N 2 O emissions for production systems with cereal yields >10 Mg ha −1 (maize), 6.6 Mg ha −1 (wheat) or 6.8 Mg ha −1 (rice), respectively. This highlights that N use efficiency indicators can be used as valuable proxies for reconciling trade‐offs between crop production and N 2 O mitigation. For all three major staple crops, reducing N fertilization by up to 30%, optimizing the timing and placement of fertilizer application or using enhanced‐efficiency N fertilizers significantly reduced yield‐scaled N 2 O emissions at similar or even higher cereal yields. Our data‐driven assessment provides some key guidance for developing effective and targeted mitigation and adaptation strategies for the sustainable intensification of cereal production.

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Emission characteristics of intermediate volatility organic compounds from a Chinese gasoline engine under varied operating conditions: Influence of fuel, velocity, torque, rotational speed, and after-treatment device - Rongzhi Tang; Song Guo; Kai Song; Ying Yu; Rui Tan; Hui Wang; Kefan Liu; Ruizhe Shen; Shiyi Chen; Limin Zeng; Zhou Zhang; Wenbin Zhang; et al. (Science of The Total Environment, 2024)

Forager-farmer transition at the crossroads of East and Southeast Asia 4900 years ago - Minmin Ma; Minxia Lu; Rui Sun; Zhonghua Zhu; Dorian Q. Fuller; Jianxin Guo; Guanglin He; Xiaomin Yang; Lingling Tan; Yongxiu Lu; Jiajia Dong; Ruiliang Liu; et al. (Science Bulletin, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Fluid evolution and gas enrichment in the Wufeng-Longmaxi shale reservoirs of the eastern Sichuan Basin, SW China - Tao Luo; Xiaowen Guo; Zhiliang He; Tian Dong; Ze Tao; Rui Yang; Keqing Wang (Journal of Asian Earth Sciences, 2024)

Electrospinning is a potential way for preparing edible plant protein-based nanofibers with porous surface using safflower seed meal - Yanling Yang; Chuang Peng; Dong Zeng; Zhengjie Yang; Xiaohu Wang; Shuang Zhang; Yucheng Bai; Lujing Kuang; Lizhi Guo; Yonghua Qin; Hairong Xiong; Jiawei Wan; et al. (Food Hydrocolloids, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Effects of microplastic properties and dissolved organic matter on phosphorus availability in soil and aqueous mediums - Runze Wang; Lin Yang; Miaomiao Guo; Xiaohua Lin; Rui Wang; Shengli Guo (Environmental Pollution, 2024)

Mechanical analysis of toppling failure using FDEM: A case study for soft-hard interbedded anti-dip rock slope - Hui Guo; Chengzeng Yan; Guohua Zhang; Rui Xu; Tie Wang; Yu-Yong Jiao (Computers and Geotechnics, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Correction to: Protective Efect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2024)

A study on the cyclic shear and particle breakage characteristics of the interface between steel and calcareous sand - Rui Wang; Jukun Guo; Shengyou Lei; Xiaowei Wang; Wentao Rong; Zhihua Yu (Marine Georesources & Geotechnology, 2023)

Dietary supplementation with polysaccharides from Rhizoma dioscoreae resulting in the enhanced immunity and the structural modulation of the intestinal microbiota in Luciobarbus capito - Yuan Sun; Xiaowei Hu; Xianwei Meng; Rui Liu; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Liang Luo (Aquaculture, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

Dispersal and parasitic ability of Anisopteromalus calandrae (Hymenoptera: Pteromalidae) against Lasioderma serricorne (Coleoptera: Anobiidae) larvae in an experimental warehouse - Yafei Guo; Jianhua Lü; Chunqi Bai; Chao Guo; Yong Huang; Rui Wang (Journal of Stored Products Research, 2023)

pH-responsive ZIF-8 film-coated mesoporous silica nanoparticles for clean, targeted delivery of fungicide and environmental hazard reduction - Yingjian Ma; Yinmin Wang; Rui Zhao; Zhijie Wang; Shuang Li; Meng Yu; Sen Pang; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Efficient wastewater disinfection through FeOOH-mediated photo-Fenton reaction: A review - Chen Wang; Peng Shi; Zhaobo Wang; Rui Guo; Junhua You; Hangzhou Zhang (Journal of Environmental Chemical Engineering, 2023)

Combining vegetation, color, and texture indices with hyperspectral parameters using machine-learning methods to estimate nitrogen concentration in rice stems and leaves - Dunliang Wang; Rui Li; Tao Liu; Shengping Liu; Chengming Sun; Wenshan Guo (Field Crops Research, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Thermokarst lake susceptibility assessment using machine learning models in permafrost landscapes of the Arctic - Rui Wang; Lanlan Guo; Yuting Yang; Hao Zheng; Hong Jia; Baijian Diao; Hang Li; Jifu Liu (Science of The Total Environment, 2023)

Distribution, sources, and potential health risks of fluoride, total iodine, and nitrate in rural drinking water sources of North and East China - Shier Huang; Jiaxun Guo; Yu Xie; Rui Bian; Nan Wang; Weixiao Qi; Huijuan Liu (Science of The Total Environment, 2023)

Cleanable natural-sugar-alcohol-based polyester membrane for highly efficient molecular separation - Xiongwei Luo; Yue Wang; Yaoli Guo; Qieyuan Gao; Rui Zhao; Yanyan Liu; Riri Liu; Lei Jiang; Zhaohuan Mai; Hideto Matsuyama; Pengrui Jin (Resources, Conservation and Recycling, 2023)

Evaluating soil water movement and soil water content uniformity under sprinkler irrigation with different soil texture and irrigation uniformity using numerical simulation - Rui Chen; Hong Li; Jian Wang; Xin Guo; Yu Xiang (Journal of Hydrology, 2023)

A new method for pre-enrichment of gallium and lithium based on mode of occurrence in coal gangue from Antaibao surface mine, Shanxi Province, China - Shiqi Dai; Fengshuai Sun; Lei Wang; Lanhao Wang; Rui Zhang; Han Guo; Yaowen Xing; Xiahui Gui (Journal of Cleaner Production, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Unexpected moderate contribution of intermediate volatility organic compounds from gasoline vehicle emission to secondary organic aerosol formation in summer of Beijing - Rongzhi Tang; Song Guo; Quanyang Lu; Kai Song; Yuanzheng Gong; Rui Tan; Kefan Liu; Hui Wang; Ying Yu; Ruizhe Shen; Shiyi Chen; Limin Zeng; et al. (Atmospheric Research, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

Influence of Auxiliary Pipelines of the Deepwater Drilling Riser on the Dynamic Characteristics of the Subsea Wellhead - Jinduo Wang; Yanbin Wang; Deli Gao; Rui Li; Liurui Guo (Journal of Marine Science and Engineering, 2023)
During deepwater drilling, the subsea wellhead will be subjected to dynamic loads transmitted from the marine environment, floating drilling platform, riser, and blowout preventer (BOP). Therefore, complex dynamic responses will be induced, which will seriously affect the safety of the subsea wellhead. In this paper, considering the effect of auxiliary pipelines on the riser, a novel entire mechanical model of the floating platform–riser–BOP–subsea wellhead is established. By using the finite-difference method, the governing equations are solved. Finally, the dynamic bending moment and stress distribution of the subsea wellhead are obtained. Moreover, the model is verified by numerical simulation in Orcaflex. On this basis, the influence of the wave height, wave period, sludge height of the subsea wellhead, rotational stiffness of the lower flexible joint, and wall thickness of the conductor on the dynamic characteristics of the subsea wellhead is discussed. Analysis results show that the theoretical analysis results are in good agreement with the numerical simulation. The auxiliary pipelines have important influence on the dynamic characteristics of the subsea wellhead. Wave period is the most important factor affecting the mechanical behavior of the subsea wellhead. Wave height, wall thickness of the conductor, and sludge height are secondary factors affecting the mechanical behavior of the subsea wellhead. The rotational stiffness of the lower flexible joint has little influence on the mechanical behavior of the subsea wellhead. By solving the optimized mechanical model proposed in this paper, the dynamic characteristic of the subsea wellhead conforms more to the actual deepwater drilling conditions. This study has reference significance for the design and mechanical control of the subsea wellhead in deepwater drilling.

Optimizing the performance of Fe-based metal-organic frameworks in photo-Fenton processes: Mechanisms, strategies and prospects - Zhaobo Wang; Ying Cheng; Chen Wang; Rui Guo; Junhua You; Hangzhou Zhang (Chemosphere, 2023)

Gravity-driven membrane system treating heavy metals-containing secondary effluent: Improved removal of heavy metals and mechanism - Xiaobin Ma; Yanrui Wang; Le Tong; Jiaoying Luo; Rui Chen; Yuanxin Wang; Xishou Guo; Jinlong Wang; Zhiwei Zhou; Jingyao Qi; Guibai Li; Heng Liang; et al. (Chemosphere, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Effect of Triton X-100 on Shiraia laccase production and its application in triclosan biodegradation - Rui Peng Cong; Yan Hua Guo; Jian Qin Zhou; Jian Wen Wang (Sustainable Chemistry and Pharmacy, 2023)

Soil pore structure mediates the effects of soil oxygen on the dynamics of greenhouse gases during wetting–drying phases - Yanling Du; Shengli Guo; Rui Wang; Xiaotong Song; Xiaotang Ju (Science of The Total Environment, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Boosting PFOA photocatalytic removal from water using highly adsorptive and sunlight-responsive ZIF67/MIL-100(Fe) modified C3N4 - Peidong Su; Chunhui Zhang; Yu Liu; Junke Zhang; Ridha Djellabi; Rui Wang; Junqiang Guo; Rui Zhang; Hongwei Guo; Xiang Ding; Xinyue Liu (Journal of Environmental Chemical Engineering, 2023)

Triassic convergence and tectonic evolution of the West Qinling orogen: Constraints from reflection-seismology imaging - Huilin Li; Rui Gao; Xingfu Huang; Haiyan Wang; Xiaoyu Guo; Hongda Liang; Xiaomiao Tan; Xiaohui Liu; Zhen Yang (Gondwana Research, 2023)

Acetylcholine (ACh) enhances Cd tolerance through transporting ACh in vesicles and modifying Cd absorption in duckweed (Lemna turionifera 5511) - Lin Yang; Xu Ma; Yuhan Guo; Yuman He; Yunwen Yang; Wenqiao Wang; Ziyi Xu; Zhaojiang Zuo; Ying Xue; Rui Yang; Bing Han; Jinsheng Sun (Environmental Pollution, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Controllable solvent treatment of fluorinated graphite for high power density and low cathode swelling lithium primary batteries - Sen Ma; Wen Liu; Daoming Zhang; Cheng Yang; Ying Luo; Xiaobing Lou; Rui Guo; Yong Wang; Jingying Xie (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Risk factors for thrombocytopenia in patients receiving linezolid therapy: a systematic review and meta-analysis - Dan Zhang; Yasi Xu; Xiang Wang; Leping Hou; Mengyu Xing; Shuang Xu; Rui Guo; Ying Luo (European Journal of Clinical Pharmacology, 2023)

Polarity-extended liquid chromatography-triple quadrupole mass spectrometry for simultaneous hydrophilic and hydrophobic metabolite analysis - Rui Guo; Qisheng Zhong; Jiaqi Liu; Peiming Bai; Zongpeng Wang; Jieling Kou; Peijie Chen; Jie Zhang; Bo Zhang (Analytica Chimica Acta, 2023)

Temporal variation of per- and polyfluoroalkyl substances (PFASs) abundances in Shenzhen Bay sediments over past 65 years - Danxu Guo; Yang Zhou; Fang Chen; Zimin Wang; Haoshuai Li; Nan Wang; Huayang Gan; Shuhong Fang; Rui Bao (Marine Pollution Bulletin, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

A mega study of antibiotics contamination in Eastern aquatic ecosystems of China: occurrence, interphase transfer processes, ecotoxicological risks, and source modeling - Abdul Qadeer; Guo Rui; Liu Yaqing; Dai Ran; Chengyou Liu; Dong Jing; Muhammad Anis; Mengyang Liu; Shuhang Wang; Xia Jiang; Xingru Zhao (Journal of Hazardous Materials, 2023)

Anaerobic selenite-reducing bacteria and their metabolic potentials in Se-rich sediment revealed by the combination of DNA-stable isotope probing, metagenomic binning, and metatranscriptomics - Rui Xu; Max Kolton; Wan Tao; Xiaoxu Sun; Pingzhou Su; Duanyi Huang; Miaomiao Zhang; Zhaohui Yang; Zhaohui Guo; Hanbing Gao; Qi Wang; Baoqin Li; et al. (Journal of Hazardous Materials, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Antimicrobial hydrogel microneedle loading verteporfin promotes skin regeneration by blocking mechanotransduction signaling - Chengxiu Wei; Chuangang You; Liming Zhou; Huiling Liu; Shihao Zhou; Xingang Wang; Rui Guo (Chemical Engineering Journal, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Reduced Survival and Resistance of Rhodotorula mucilaginosa Following Inhibition of Pigment Production by Naftifine - Nur Fazleen Binti Idris; Qianying Jia; He Lu; Yanan Guo; Yang Wang; Rui Hao; Zeng Tu (Current Microbiology, 2023)

Predictive value of serum proteomic biomarkers for noise-induced hearing loss - Yuqiang Lun; Jiawei Chen; Peiheng Lu; Hao Yuan; Pengwei Ma; Weilong Wang; Rui Liang; Siyu Li; Wei Gao; Xuerui Ding; Zi Wang; Jianing Guo; et al. (Environmental Science and Pollution Research, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Hepatoprotective effects of chlorogenic acid on mice exposed to aflatoxin B1: Modulation of oxidative stress and inflammation - Kang Cheng; Jingyi Niu; Jinyan Zhang; Yining Qiao; Guorun Dong; Rui Guo; Xiaotong Zheng; Zhihua Song; Jin Huang; Jinrong Wang; Yong Zhang (Toxicon, 2023)

Resistance mechanism of partially embedded pipelines considering the influence of temperature fields - Hongyu Wang; Kuanjun Wang; Zhen Guo; Shengjie Rui; Zhenkui Wang (Ocean Engineering, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Effects of different water-cooled heat sinks on the cooling system performance in a data center - Wei He; Jifang Zhang; Hailong Li; Rui Guo; Shengchun Liu; Xiaohui Wu; Jie Wei; Yulin Wang (Energy and Buildings, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Changes in fungal diversity and key-stone taxa along soil-eroding catena - Runze Wang; Lin Yang; Xin Gao; Shengli Guo; Rui Wang (Applied Soil Ecology, 2023)

Assessment of radiation doses and DNA damage in pediatric patients undergoing interventional procedures for vascular anomalies - Ya Ma; Lei Guo; Lianying Fang; Dianjun Hou; Rui Chen; Xiaoshan Wang; Xuesong Mao; Zihan Zhao; Yingmin Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Prenatal bisphenol S exposure induces hepatic lipid deposition in male mice offspring through downregulation of adipose-derived exosomal miR-29a-3p - Rui Zhang; Jingyao Guo; Yupeng Wang; Rundong Sun; Guangzhu Dong; Xinru Wang; Guizhen Du (Journal of Hazardous Materials, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Systematic exploration of transcriptional responses of interspecies interaction between Karenia mikimotoi and Prorocentrum shikokuense - Jian-Wei Zheng; Guo-Hui He; Rui-Xia Xu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Role of soil organic matter composition and microbial communities on SOC stability: Insights from particle-size aggregates - Xin Gao; Asmeret Asefaw Berhe; Yaxian Hu; Lanlan Du; Fangbin Hou; Shengli Guo; Rui Wang (Journal of Soils and Sediments, 2023)

A robust activatable two-photon fluorescent probe for endogenous formaldehyde biomarker visualization diagnosis and evaluation of diabetes mellitus - Jiangyan Wang; Jiangfeng Li; Lizhen Xu; Dan Tan; Rui Guo; Weiying Lin (Analytica Chimica Acta, 2023)

Characteristics of drought, low temperature, and concurrent events of maize in Songliao Plain - Yunmeng Zhao; Ying Guo; Rui Wang; Kaiwei Li; Guangzhi Rong; Jiquan Zhang; Chunli Zhao (International Journal of Climatology, 2023)
Maize is susceptible to drought and low temperatures. In recent years, drought, low temperatures, and their composite events have often occurred during the growth period of maize, causing a huge impact. In this study, maize in the Songliao Plain was used as the research object. Based on the crop water surplus deficit index (CWSDI) and heat index (F(T)), combined with the Theil–Sen median and Mann–Kendall tests (Sen–MK) and empirical orthogonal function (EOF), the temporal trends and spatial patterns of drought and low temperatures in different growth periods of maize were obtained. Copula modelling was used to analyse the joint probability distribution and return period of drought and low temperatures. The results showed that the temporal variation trend of the CWSDI was significantly different at different growth periods of maize, and there were different trends and spatial modal distributions. However, the temporal variation trend of F(T) was similar, showing a downward trend over the entire region. There was no obvious asymmetry or skew‐dependent structure in the distribution of concurrent events of drought and low temperature; however, the joint probability contours of different growth periods were biased to the upper left. The recurrence period of drought and low‐temperature concurrent events was within 2 years, and the recurrence period was basically between 2 and 5 years, with a reduction in drought or low temperatures.

Nanoencapsulation-based fabrication of eco-friendly pH-responsive pyraclostrobin formulations with enhanced photostability and adhesion to leaves - Yingjian Ma; Linjie Li; Rui Zhao; Zhe Sun; Yinmin Wang; Meng Yu; Shouhe Pan; Xinyu Guo; Yong Xu; Hongmei Wang; Ping Wang; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

Simultaneously mapping loci related to two plant architecture traits by phenotypic recombination BSA/BSR in peanut (Arachis hypogaea L.) - Xiaona Yu; Yaoyao Li; Xinyuan Cui; Xianheng Wang; Jihua Li; Rui Guo; Fanzhuang Yan; Shaojing Zhang; Ruihua Zhao; Danlei Song; Tong Si; Xiaoxia Zou; et al. (Theoretical and Applied Genetics, 2023)

The Impact of Long-term Phosphorus Fertilization on Soil Aggregation and Aggregate-Associated P Fractions in Wheat-Broomcorn Millet/Pea Cropping Systems - Asif Khan; Shengli Guo; Wang Rui; Binghui He; Tianyang Li; Umer Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Effects of saline-alkali stress on the tissue structure, antioxidation, immunocompetence and metabolomics of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Science of The Total Environment, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Corrigendum to “A quantitative proteomic analyses of primary myocardial cell injury induced by heat stress in chicken embryo” [J. Therm. Biol. 112 (2023) 103461] - Rui Wang; Yanli Guo; Zhaoguo Shi; Shizhen Qin (Journal of Thermal Biology, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

A constitutive model for caprock siltstone subject to three-dimensional compression with emphasis on plastic potential and hardening law - Zhechao Wang; Weichuan Shi; Xia-ting Feng; Liping Qiao; Rui Kong; Jiafan Guo (Engineering Geology, 2023)

Hybrid plasma-thermal system for methane conversion to ethylene and hydrogen - Rui Liu; Yingzi Hao; Tong Wang; Li Wang; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2023)

Engineering triple internal electric fields in Ag NWs@BaTiO3 composites for ultrasonic-visible-light driven antibacterial activity - Guoqiang Shu; Yaqi Lin; Rui Zhong; Xiaofan Su; Shanhong Guo; Chao Wang; Changan Zhou; Lei Song; Li Xie; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Meta-heuristic Techniques in Microgrid Management: A Survey - Zedong Zheng; Shengxiang Yang; Yinan Guo; Xiaolong Jin; Rui Wang (Swarm and Evolutionary Computation, 2023)

Divergent responses of phoD- and pqqC-harbouring bacterial communities across soil aggregates to long fertilization practices - Lin Yang; Lanlan Du; Weijia Li; Rui Wang; Shengli Guo (Soil and Tillage Research, 2023)

Characteristics of silicon and phytolith distribution in bamboo (Ferrocalamus strictus): variations between different organs and ages - Rui Xu; Honglan He; Huijun Guo; Fangwei Zhu; Shuguang Wang; Cefeng Dai; Xiaofeng Zheng; Dongbo Xie; Haoming Li; Changming Wang; Hui Zhan (Review of Palaeobotany and Palynology, 2023)

Large-scale mapping of solifluction terraces in the southeastern Tibetan Plateau using high-resolution satellite images and deep learning - Ronggang Huang; Liming Jiang; Zhida Xu; Rui Guo; Fujun Niu; Hansheng Wang (Geomorphology, 2023)

A pH/cellulase dual stimuli-responsive cellulose-coated metal–organic framework for eco-friendly fungicide delivery - Yingjian Ma; Meng Yu; Yinmin Wang; Shouhe Pan; Xuelin Sun; Rui Zhao; Zhe Sun; Rui Gao; Xinyu Guo; Yong Xu; Xuemin Wu (Chemical Engineering Journal, 2023)

Managing iodine and tin based defects for efficient and stable mixed Sn-Pb perovskite solar cells - Yanjun Xing; Zhiqiang Deng; Tonghui Guo; Zequn Zhang; Qidong Tai; Rui Zhao; Jiaxing Xiong; Qiuxiang Wang; Like Huang; Xiaohui Liu; Ziyang Hu; Yuejin Zhu; et al. (Chemical Engineering Journal, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

A novel solvent system of polyamides achieves new application in ZIBs by aggregation induced Lewis acid-base centers - Murong Xi; Zhenjie Liu; Rui Sheng; Jiafeng Zhu; Yong Guo; Juan Ding; Xingchao Wang; Yue Zhang; Lei Wang; Zhipeng Sun; Wenjun Zhang; Jiulin Wang; et al. (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Quantify the effect of manure fertilizer addition and optimal nitrogen input on rainfed wheat yield and nitrogen requirement using nitrogen nutrition index - Pengzhao Liu; Xingyu Guo; Dong Zhou; Qi Zhang; Xiaolong Ren; Rui Wang; Xiaoli Wang; Xiaoli Chen; Jun Li (Agriculture, Ecosystems & Environment, 2023)

Morphological alterations in C57BL/6 mouse intestinal organoids as a tool for predicting chemical-induced toxicity - Ziwei Wang; Shen Chen; Yaqin Pang; Lizhu Ye; Qi Zhang; Xinhang Jiang; Rui Zhang; Miao Li; Zhanyu Guo; Yue Jiang; Daochuan Li; Xiumei Xing; et al. (Archives of Toxicology, 2023)

Transcriptomic analysis of juvenile cobia in response to hypoxic stress - Jian-Sheng Huang; Zhi-Xiong Guo; Jian-Dong Zhang; Wei-Zheng Wang; Zhong-Liang Wang; Rui-Tao Xie; Eric Amenyogbe; Gang Chen (Aquaculture International, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Potential negative effects of illumination on gravity-driven membrane system in treating sulfamethoxazole-containing water - Rui Chen; Han Zhang; Dachao Lin; Jinlong Wang; Yuanqing Guo; Xiaobin Tang; Weijia Gong; Heng Liang (Resources, Conservation and Recycling, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Pregnancy and lactation mixed exposure to lead, cadmium, and mercury alters maternal-offspring single heavy metal load: A factorial design - Guihua Du; Fankun Zhou; Lu Ouyang; Kai Wang; Shaoqi Rao; Rui Su; Yanhui Zhu; Kechu Guo; Jinmei Xiao; Jie Xie; Qi Li; Chang Feng; et al. (International Journal of Hygiene and Environmental Health, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Differences in the patterns and mechanisms of leaf and ecosystem-scale water use efficiencies on the Qinghai-Tibet Plateau - Xiang Wang; Guo Chen; Mingquan Wu; Xiaozhen Li; Qi Wu; Peng Wang; Hui Zeng; Rui Yang; Xiaolu Tang (CATENA, 2023)

Applications and grants of National Natural Science Foundation of China’s General Program in cardiovascular research: a 10-year review - Juejin Wang; Zhaoyang Chen; Hongchang Guo; Rui Wang; Ruijuan Sun (Science China Life Sciences, 2023)

Genome-wide identification and expression analysis of the cotton patatin-related phospholipase A genes and response to stress tolerance - Yunxiao Wei; Zhili Chong; Chao Lu; Kaili Li; Chengzhen Liang; Zhigang Meng; Yuan Wang; Sandui Guo; Liangrong He; Rui Zhang (Planta, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

SLP-2 regulates the generation of reactive oxygen species and the ERK pathway to promote papillary thyroid carcinoma motility and angiogenesis - Jianping Chen; Duting Wang; Rui Xu; Ting Yao; Yu Guo; Qi Liu; Erlong Yang; Zhengqing Wu; Zhenyu Xu (Tissue and Cell, 2023)

Antimicrobial peptide CB-M exhibits direct antifungal activity against Botrytis cinerea and induces disease resistance to gray mold in cherry tomato fruit - Xiaomin Yang; Yating Wang; Hanyue Jiang; Rui Song; Yongguo Liu; Honglian Guo; Demei Meng (Postharvest Biology and Technology, 2023)

A quantitative proteomic analyses of primary myocardial cell injury induced by heat stress in chicken embryo - Rui Wang; Yanli Guo; Zhaoguo Shi; Shizhen Qin (Journal of Thermal Biology, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

Inhibition of ice recrystallization by tamarind (Tamarindus indica L.) seed polysaccharide and molecular weight effects - Xianbao Sun; Rui Guo; Yuxing Kou; Hong Song; Taijie Zhan; Jinhong Wu; Lihua Song; Hui Zhang; Fan Xie; Jiangmei Wang; Zibo Song; Yan Wu (Carbohydrate Polymers, 2023)

Experimental Study of Vibration Reduction Effect of Barrier Holes Under Blasting - Jianbo Zhu; Rui Zhao; Yashi Li; Yankun Ma; Jianxin Wang; Qi Peng; Jun Guo (Rock Mechanics and Rock Engineering, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

Electroacupuncture promotes remyelination and alleviates cognitive deficit via promoting OPC differentiation in a rat model of subarachnoid hemorrhage - Yingwen Wang; Xiaomin Yang; Yunchuan Cao; Xiaoguo Li; Rui Xu; Jin Yan; Zongduo Guo; Shanquan Sun; Xiaochuan Sun; Yue Wu (Metabolic Brain Disease, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Immune and intestinal microbiota responses to heat stress in Chinese mitten crab (Eriocheir sinensis) - Zhiqiang Li; Zhigang Zhao; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Yuhong Yang (Aquaculture, 2023)

Secondary organic aerosol formation in China from urban-lifestyle sources: Vehicle exhaust and cooking emission - Zirui Zhang; Wenfei Zhu; Min Hu; Hui Wang; Lizi Tang; Shuya Hu; Ruizhe Shen; Ying Yu; Kai Song; Rui Tan; Zheng Chen; Shiyi Chen; et al. (Science of The Total Environment, 2023)

Metabolomics analysis reveals the response mechanism to carbonate alkalinity toxicity in the gills of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Multifunctional lysosome-targetable fluorescent probe for imaging peroxynitrite in acute liver injury model - Kai Wang; Rui Guo; Xu-Yang Chen; Yu-Shun Yang; Lu-Qin Qiao; Ming-Lin Wang (Chemical Engineering Journal, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

More intelligent and efficient thermal environment management: A hybrid model for occupant-centric thermal comfort monitoring in vehicle cabins - Xinglei He; Xiaohan Zhang; Rui Zhang; Jiaxin Liu; Xiaoyu Huang; Jinchen Pei; Jingyang Cai; Fen Guo; Yichun Wang (Building and Environment, 2023)

Water-soluble brown carbon in PM2.5 at two typical sites in Guanzhong Basin: Optical properties, sources, and implications - Xiaofei Li; Feng Yu; Yiying Song; Chao Zhang; Fangping Yan; Zhaofu Hu; Yali Lei; Lekhendra Tripathee; Rui Zhang; Jingning Guo; Yuqin Wang; Qingcai Chen; et al. (Atmospheric Research, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Selenite Ameliorates Cadmium-induced Cytotoxicity Through Downregulation of ROS Levels and Upregulation of Selenoprotein Thioredoxin Reductase 1 in SH-SY5Y Cells - Hecheng Wang; Shibo Sun; Yan Ren; Rui Yang; Jianli Guo; Yu Zong; Qiuxian Zhang; Jing Zhao; Wei Zhang; Weiping Xu; Shui Guan; Jianqiang Xu (Biological Trace Element Research, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

Characterization of a Hyaluronidase-Producing Bacillus sp. CQMU-D Isolated from Soil - Lu Wang; Qianqian Liu; Rui Hao; Jing Xiong; Junxing Li; Yanan Guo; Lu He; Zeng Tu (Current Microbiology, 2022)

Comparative transcriptome analysis of leaves of sour jujube seedlings under salt stress - Ruiheng Lyu; Rui Wang; Cuiyun Wu; Yajing Bao; Peng Guo (Acta Physiologiae Plantarum, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Human Urine-Derived Stem Cells Improve Partial Bladder Outlet Obstruction in Rats: Preliminary Data and microRNA-mRNA Expression Profile - Menjiang Tu; Rui Wang; Pei Zhu; Qingqing Wang; Bishao Sun; Keshi Lu; Jiawei Zhang; Weijie Xie; Huan Guo; Shulin Li; Yuqi Wu; Xiangwei Wang (Stem Cell Reviews and Reports, 2022)
Partial bladder outlet obstruction (pBOO) often results in bladder tissue inflammation and remodeling. As human urine-derived stem cells (USCs) have demonstrated therapeutic benefits, we used a rat model to investigate the effect of USCs on bladder function and explore the miRNA and gene expression profiles in bladder tissue using RNA sequencing. Eighteen rats were assigned to a sham surgery group, pBOO group, and pBOO+USC group (six biweekly treatments). Routine urodynamic monitoring, analysis of detrusor muscle strips, and pathophysiology assessments were conducted. Finally, altered miRNA and mRNA expression profiles of bladder tissue were examined using RNA sequencing and bioinformatics analysis. After USC treatment, elevated bladder compliance and maximal voiding pressure, declined end filling pressure and voided volume, and improved detrusor muscle contractility and carbachol sensitivity were found. Histology and TUNEL assay revealed reduced collagen deposition and muscle cell apoptosis in bladder tissue. The differential expression of eight miRNAs was reversed by USC treatment. Two large nodes (miR-142 and miR-9a) were identified in the miRNA-gene interaction network in the USC-treated group. The Kyoto Encyclopedia of Genes and Genomes analysis revealed enrichment of multiple significant pathways, including those involved in necroptosis and cytokine-cytokine receptor interactions. This is the first study to demonstrate the protective effect of USCs on bladder function and remodeling in pBOO rats. The miRNA and mRNA expression levels differed in the bladder of pBOO rats with and without USC treatment. Although the mechanism underlying these effects has not been fully elucidated, necroptosis and cytokine-cytokine receptor interaction-related pathways may be involved. Graphical abstract

Protective Effect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2022)

Combined Effects of Eco-Substrate and Carbon Addition on Water Quality, Fish Performance and Nutrient Budgets in the Pond Polyculture System - Kun Guo; Zhigang Zhao; Jun Xie; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Xiaoli Huang (Fishes, 2022)
Traditional aquaculture can cause serious environmental pollution. Biofilm and biofloc technology have the potential to limit aquaculture pollution. An outdoor experiment was conducted to evaluate the combined effects of eco-substrates and carbon addition on water quality, fish performance and nutrient budgets in the pond polyculture system. In the treatment group, the total ammonia nitrogen, nitrate nitrogen, nitrite nitrogen, and total nitrogen of the water were significantly lower compared to the control group (p 92%) and P (>95%) input during the experiment. Comprehensive accumulation was the main N (>58%) and P (>69%) output. The N and P feed input and comprehensive accumulation output declined in the treatment group. The N utilization efficiency in the experimental group increased slightly (p > 0.05), while the P utilization efficiency in the experimental group was significantly higher compared to the control (p

Effects of Alkalinity on the Antioxidant Capacity, Nonspecific Immune Response and Tissue Structure of Chinese Mitten Crab Eriocheir sinensis - Mingshuai Li; Shihui Wang; Zhigang Zhao; Liang Luo; Rui Zhang; Kun Guo; Lanlan Zhang; Yuhong Yang (Fishes, 2022)
The effects of various levels of alkalinity stress (0, 18.25, 35.41, 52.53 and 69.74 mmol/L) in Chinese mitten crab (Eriocheir sinensis) were investigated by means of measuring hepatopancreas antioxidant system and serum nonspecific immune system-related indices at 0, 12, 24, 48 and 96 h, hepatopancreas tissue structure at 96 h. The activities of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and aspartate aminotransferase (AST) in each concentration group generally showed a trend of a first increasing and then decreasing during the 96-h stress process (p 0.05). The activities of CAT, GSH and AST in all treatment reached peak values at 24–48 h. At 96 h of alkalinity stress, the activities of GSH, alanine aminotransferase (ALT), acid phosphatise (ACP) and alkaline phosphatise (AKP) in the 18.25 mmol/L group were not significantly different with the control group (p > 0.05). The activities of SOD and CAT in the 52.53 and 69.74 mmol/L treatment were significantly lower than those in the control group (p

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

LncRNA SNHG14 is beneficial to oxygen glucose deprivation/reoxygenation-induced neuro-2a cell injury via mir-98-5p sequestration-caused BCL2L13 upregulation - Gaolian Zhang; Jianhui Guo; Jing Zeng; Xiaoning Zhang; Rui Chen; Gang Wang; Weibin Liang (Metabolic Brain Disease, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

A novel therapeutic strategy for atherosclerosis: autophagy-dependent cholesterol efflux - Haipeng Guo; Dongmei Wei; Rui Liu; Chao Zhang; Song Jiang; Weijia Wang; Hongzhe Hu; Lijuan Shen; Xiaofei Liang (Journal of Physiology and Biochemistry, 2022)

Population Genetic Diversity and Differentiation of Mitten Crab, Genus Eriocheir, Based on Microsatellite Markers - Shihui Wang; Liang Luo; Rui Zhang; Kun Guo; Wei Xu; Zhigang Zhao (Fishes, 2022)
Mitten crab, Eriocheir sensu stricto, is an important indigenous aquatic species and food source in Eastern Asia. Genetic diversity is an important prerequisite for the conservation and utilization of germplasm resources. However, the genetic diversity and differentiation of Eriocheir s. s. remains unclear. This study evaluated population genetic diversity and genetic differentiation of three Eriocheir s. s. populations from Suifenhe (SFH), Liaohe (LH), and Nanliujiang (NLJ), China, based on 19 microsatellite markers. The mean observed number of alleles (Na) was 22.84 alleles, and the mean polymorphism information content (PIC) was 0.86, which demonstrated high genetic diversity. The allele frequency distribution showed an “L” shape, ranging from 0.01 to 0.74. The genetic diversity parameter values of the LH population were higher than those of the other two populations. All pairwise FST values showed significant differences among the three Eriocheir s. s. populations (p

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Establishment and optimization of PEG-mediated protoplast transformation in the microalga Haematococcus pluvialis - Chunli Guo; Muhammad Anwar; Rui Mei; Xinyi Li; Di Zhao; Yanan Jiang; Jieyi Zhuang; Chen Liu; Chaogang Wang; Zhangli Hu (Journal of Applied Phycology, 2022)
Genetic manipulation of Haematococcus pluvialis is difficult because of the lack of a stable and convenient transformation system. The pH124-EGFP-Ble vector containing ble as a selective gene and EGFP as a reporter gene was constructed and employed for effective transformation. H. pluvialis protoplasts were obtained by treating with cellulase and macerozeme. Then polyethylene glycol-mediated transformation was established by incubating the protoplast with the vector. To improve the transformation efficiency of H. pluvialis protoplasts, the transformation system was optimized in consideration of different influencing factors, including zeomycin concentration, growth stage, amount of transformed vector, linearization of the vector, and duration of low-intensity illumination. The integration and expression of ble and EGFP was confirmed in the transformants. Moreover, the optimal combination for protoplast transformation of H. pluvialis was determined to be 5 µg of the linearized vector used to transform cells in the log growth phase, and then the transformed protoplasts allowed to recover under low-intensity illumination for 6 h. This study represents and describes the successful development of an H. pluvialis transformation protocol using protoplasts, which will enable convenient genetic manipulation of this important algal species.

IDDLncLoc: Subcellular Localization of LncRNAs Based on a Framework for Imbalanced Data Distributions - Yan Wang; Xiaopeng Zhu; Lili Yang; Xuemei Hu; Kai He; Cuinan Yu; Shaoqing Jiao; Jiali Chen; Rui Guo; Sen Yang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Assessing residual motor function in patients with disorders of consciousness by brain network properties of task-state EEG - Lipeng Zhang; Rui Zhang; Yongkun Guo; Dexiao Zhao; Shizheng Li; Mingming Chen; Li Shi; Dezhong Yao; Jinfeng Gao; Xinjun Wang; Yuxia Hu (Cognitive Neurodynamics, 2022)

Toxicities of nanomaterials and metals to rice under low atmospheric pressure - Kerui Guo; Dongheng Fu; Muhammed Adeel; Yunze Shen; Kexiang Wang; Yi Hao; Tonghao Bai; Yaoyao Wang; Yukui Rui (Acta Physiologiae Plantarum, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Manganese Mitigates Heat Stress–Induced Apoptosis by Alleviating Endoplasmic Reticulum Stress and Activating the NRF2/SOD2 Pathway in Primary Chick Embryonic Myocardial Cells - Shizhen Qin; Rui Wang; Defu Tang; Shijiao Qin; Yanli Guo; Zhaoguo Shi (Biological Trace Element Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Study on excavation stability of shallow rectangular shield pipe jacking tunnel - Wantao Ding; Zhongrong Wang; Xinghang Huang; Rui Chen; Lewen Zhang; Yingjie Zheng; Xiaowei Guo (Arabian Journal of Geosciences, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

A two-phase comprehensive NSCLC prognostic study identifies lncRNAs with significant main effect and interaction - Jing Zhu; Jinxing Guan; Xinyu Ji; Yunjie Song; Xiaoshuang Xu; Qianqian Wang; Quanan Zhang; Renhua Guo; Rui Wang; Ruyang Zhang (Molecular Genetics and Genomics, 2022)
Long noncoding RNA (lncRNA) are involved in regulating physiological behaviors for various malignant tumors, including non-small-cell lung cancer (NSCLC). However, few studies comprehensively evaluated both lncRNA–lncRNA interaction effects and main effects of lncRNA on overall survival of NSCLC. Hence, we performed a two-phase designed study of lncRNA expression in tumor tissues using 604 NSCLC patients from The Cancer Genome Atlas as the discovery phase and 839 patients from Gene Expression Omnibus as the validation phase. In the discovery phase, we adopted a two-step strategy, Screening before Testing , for dimension reduction and signal detection. These candidate lncRNAs first screened out by the weighted random forest (Ranger), were then tested through the Cox proportional hazards model adjusted for covariates. Significant lncRNAs with either type of effects aforementioned were carried forward into the validation phase to confirm their significances again. As a result, in the discovery phase, 19 lncRNAs were identified by Ranger, among which five lncRNAs and one pair of lncRNA–lncRNA interaction exhibited significant effects (FDR- q ≤ 0.05) main and interaction effects on NSCLC survival, respectively, through Cox model. After the independent validation, we finally observed that one lncRNA (ENSG00000227403.1) with main effect was robustly associated with NSCLC prognosis ( HR discovery = 0.90, P = 1.20 × 10 –3 ; HR validation = 0.94, P = 4.11 × 10 –3 ) and one pair of lncRNAs (ENSG00000267121.4 and ENSG00000272369.1) had significant interaction effect on NSCLC survival ( HR discovery = 1.12, P = 3.07 × 10 –4 ; HR validation = 1.11, P = 0.0397). Our comprehensive NSCLC prognostic study of lncRNA provided population-level evidence for further functional study.

Numerical investigations on load transfer of mooring line considering chain–seabed dynamic interaction - Shengjie Rui; Zhen Guo; Lizhong Wang; Haochen Liu; Wenjie Zhou (Marine Georesources & Geotechnology, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Heavy metal pollution from copper smelting during the Shang Dynasty at the Laoniupo site in the Bahe River valley, Guanzhong Basin, China - Menglei Wu; Yana Jia; Yuzhu Zhang; Rui Wen; Jiahua Guo; Ninglian Wang; Wanqing Liu; Haijun Qiu; Haoyu Wang; Yiheng Xian; Chun Yu; Ting Yang (Journal of Geographical Sciences, 2021)

Screening and Analysis of Multiclass Veterinary Drug Residues in Animal Source Foods using UPLC-Q-Exactive Orbitrap/MS - Wentao Zhao; Rui Jiang; Wenping Guo; Chao Guo; Shilei Li; Juanqiang Wang; Shouwei Wang; Yingying Li (Bulletin of Environmental Contamination and Toxicology, 2021)
A rapid, simple, and sensitive method of detecting veterinary drug residues in animal food sources, including poultry and pork, was developed and validated. The method was optimized for over 155 veterinary drugs of 21 different classes. Sample pretreatment included a simple solid-liquid extraction step with 0.2% formic acid-acetonitrile-water and a purification step with a PRiME HLB (hydrophile-lipophile balance) solid-phase extraction cartridge. Data were collected using ultra-high-performance liquid chromatography coupled to Quadrupole-Exactive Orbitrap mass spectrometry. The limits of detection of 155 veterinary drugs ranged from 0.1 µg/kg to 10 µg/kg. The recovery rates were between 79.2 and 118.5 % in all matrices studied, with relative standard deviation values less than 15% (n = 6). The evaluated method allows the reliable screening, quantification, and identification of 155 veterinary drug residues in animal source food and has been successfully applied in authentic samples.

Lateral Hypothalamic Area Glutamatergic Neurons and Their Projections to the Lateral Habenula Modulate the Anesthetic Potency of Isoflurane in Mice - Shiyi Zhao; Rui Li; Huiming Li; Sa Wang; Xinxin Zhang; Dan Wang; Juan Guo; Huihui Li; Ao Li; Tingting Tong; Haixing Zhong; Qianzi Yang; et al. (Neuroscience Bulletin, 2021)
The lateral hypothalamic area (LHA) plays a pivotal role in regulating consciousness transition, in which orexinergic neurons, GABAergic neurons, and melanin-concentrating hormone neurons are involved. Glutamatergic neurons have a large population in the LHA, but their anesthesia-related effect has not been explored. Here, we found that genetic ablation of LHA glutamatergic neurons shortened the induction time and prolonged the recovery time of isoflurane anesthesia in mice. In contrast, chemogenetic activation of LHA glutamatergic neurons increased the time to anesthesia and decreased the time to recovery. Optogenetic activation of LHA glutamatergic neurons during the maintenance of anesthesia reduced the burst suppression pattern of the electroencephalogram (EEG) and shifted EEG features to an arousal pattern. Photostimulation of LHA glutamatergic projections to the lateral habenula (LHb) also facilitated the emergence from anesthesia and the transition of anesthesia depth to a lighter level. Collectively, LHA glutamatergic neurons and their projections to the LHb regulate anesthetic potency and EEG features.

A massive ancient river-damming landslide triggered by buckling failure in the upper Jinsha River, SE Tibetan Plateau - Yanyan Li; Xuyang Feng; Aijun Yao; Shan Lin; Rui Wang; Mingzhu Guo (Bulletin of Engineering Geology and the Environment, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Space–time variations of sea ice in Bohai Sea in the winter of 2009–2010 simulated with a coupled ocean and ice model - Rui Li; Youyu Lu; Xianmin Hu; Donglin Guo; Peng Zhao; Ning Wang; Kenneth Lee; Baiyu Zhang (Journal of Oceanography, 2021)

Automated measurement of hip–knee–ankle angle on the unilateral lower limb X-rays using deep learning - Yun Pei; Wenzhuo Yang; Shangqing Wei; Rui Cai; Jialin Li; Shuxu Guo; Qiang Li; Jincheng Wang; Xueyan Li (Physical and Engineering Sciences in Medicine, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Cloning and expression analysis of hypoxia-related gene HO in cobia - Rui-tao Xie; Eric Amenyogbe; Wei-zheng Wang; Zhi-xiong Guo; Gang Chen; Jian-sheng Huang (Aquaculture International, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

Geochemistry and zircon U-Pb ages of the Oligocene sediments in the Baiyun Sag, Zhujiang River Mouth Basin - Rui Sun; Ming Ma; Kai Zhong; Xiayang Wang; Zhao Zhao; Shuai Guo; Xingzong Yao; Gongcheng Zhang (Acta Oceanologica Sinica, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Effects of Cr(VI)-reducing bacteria on the behaviour of Cr(VI) adsorption by goethite and haematite: speciation and distribution - Chunyong Wang; Rui Wu; Jianbo Guo; Yanshan Cui (Journal of Soils and Sediments, 2020)

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Selenium Deficiency in Chickens Induces Intestinal Mucosal Injury by Affecting the Mucosa Morphology, SIgA Secretion, and GSH-Px Activity - Xianjing He; Yucai Lin; Shuai Lian; Dongbo Sun; Donghua Guo; Jianfa Wang; Rui Wu (Biological Trace Element Research, 2020)

Complete genome sequence of a novel mycovirus isolated from the phytopathogenic fungus Corynespora cassiicola in China - Yanfen Wang; Hang Zhao; Caiying Xue; Chao Xu; Yuehua Geng; Rui Zang; Yuxia Guo; Haiyan Wu; Meng Zhang (Archives of Virology, 2020)

The study on loess liquefaction in China: a systematic review - Siyue He; Xiuling Wang; Haobo Fan; Hao Wang; Rui Ren; Chunxia Guo (Natural Hazards, 2020)

Spatio-temporal characteristics of the relationship between carbon emissions and economic growth in China’s transportation industry - Li Wang; Jie Fan; Jiaoyue Wang; Yanfei Zhao; Zhen Li; Rui Guo (Environmental Science and Pollution Research, 2020)

Transcriptome Profile Analysis of Resistance Inoculated by Dryopteris crassirhizoma Dryocrassin ABBA in Potato Tubers - Wenzhong Wang; Rui Gao; Tong Zhang; Lingling Chen; Peng Feng; Zongbao Zhao; Changxu Zhang; Fanxiang Min; Shuai Yang; Qi Wei; Mei Guo; Ying Chang (American Journal of Potato Research, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Minor topography governing erosional distribution of SOC and temperature sensitivity of CO2 emissions: comparisons between concave and convex toposequence - Yao He; Yaxian Hu; Xin Gao; Rui Wang; Shengli Guo; Xianwen Li (Journal of Soils and Sediments, 2020)

Disruption of the lactate dehydrogenase and acetate kinase genes in Klebsiella pneumoniae HD79 to enhance 2,3-butanediol production, and related transcriptomics analysis - Jingping Ge; Jiawang Wang; Guangbin Ye; Shanshan Sun; Rui Guo; Gang Song; Wenxiang Ping (Biotechnology Letters, 2020)

miR477 targets the phenylalanine ammonia-lyase gene and enhances the susceptibility of the tea plant (Camellia sinensis) to disease during Pseudopestalotiopsis species infection - Shuangshuang Wang; Shengrui Liu; Lu Liu; Rui Li; Rui Guo; Xiaobo Xia; Chaoling Wei (Planta, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

The basolateral amygdala regulation of complex cognitive behaviours in the five-choice serial reaction time task - Fangyuan Yin; Hao Guo; Jingjing Cui; Yuhui Shi; Rui Su; Qiaoli Xie; Jinrui Chang; Yunpeng Wang; Jianghua Lai (Psychopharmacology, 2019)

The Functional Analysis of Selenium-Related Genes and Magnesium-Related Genes in the Gene Expression Profile Microarray in the Peripheral Blood Mononuclear Cells of Keshan Disease - Sen Wang; Rui Yan; Bin Wang; Peiling Meng; Wuhong Tan; Xiong Guo (Biological Trace Element Research, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Integrated analysis of miRNAs and their targets reveals that miR319c/TCP2 regulates apical bud burst in tea plant (Camellia sinensis) - Shengrui Liu; Xiaozeng Mi; Ran Zhang; Yanlin An; Qiying Zhou; Tianyuan Yang; Xiaobo Xia; Rui Guo; Xuewen Wang; Chaoling Wei (Planta, 2019)

Bivariate copula function-based spatial–temporal characteristics analysis of drought in Anhui Province, China - Rui Wang; Chunli Zhao; Jiquan Zhang; Enliang Guo; Danjun Li; Si Alu; Si Ha; Zhenhua Dong (Meteorology and Atmospheric Physics, 2019)

Two new sesquineolignans from the seeds of Crataegus pinnatifida and their β -amyloid aggregation inhibitory activitiy - Rui Guo; Le Zhou; Peng Zhao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Transcriptional regulation contributes more to Monascus pigments diversity in different strains than to DNA sequence variation - Xiaoyu Guo; Yao Li; Rui Zhang; Jiyuan Yu; Xinbao Ma; Mianhua Chen; Yurong Wang (World Journal of Microbiology and Biotechnology, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Metabolomics reveals the drought-tolerance mechanism in wild soybean (Glycine soja) - Xiaoxia Wang; Rui Guo; Mingxia Li; Yuan Liu; Mingli Zhao; Hui Fu; Xueying Liu; Shiyao Wang; Lianxuan Shi (Acta Physiologiae Plantarum, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

Uncommon Peptide Bond Cleavage of Glucagon from a Specific Vendor under near Neutral to Basic Conditions - Hong-Jian Zheng; Bin-Bin Shen; Jing Wang; Haibin Wang; Guo-Li Huo; Li-Rui Huang; Jian-Qing Gao; Wei-Jie Fang (Pharmaceutical Research, 2019)

The severity of drought and precipitation prediction in the eastern fringe of the Tibetan Plateau - Yang Zhao; Xiangde Xu; Liufeng Liao; Yuhong Wang; Xiaoping Gu; Rui Qin; Yunyun Guo; Zhaoping Kang; Fang Wang; Min Wang (Theoretical and Applied Climatology, 2019)

Responses of nitrification and denitrification to nitrogen and phosphorus fertilization: does the intrinsic soil fertility matter? - Ying Wang; Hongfei Ji; Rui Wang; Shengli Guo (Plant and Soil, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Depositional and diagenetic controls on the reservoir quality of Upper Triassic Chang-7 tight oil sandstones, southwestern Ordos basin, China - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Zhuopei Li; Yangjinfeng Jiang; Xueqi Yang; Rui Xie; Xiaowei Zheng (Geosciences Journal, 2019)

Highly Sensitive and Selective Fluorescent Probe for Detection of Fe3+ Based on Rhodamine Fluorophore - Yang Wang; Rui Guo; Xufeng Hou; Mengmeng Lei; Qihang Zhou; Zhihong Xu (Journal of Fluorescence, 2019)

Effects of organic-inorganic amendments on the cadmium fraction in soil and its accumulation in rice (Oryza sativa L.) - Bing Li; Lan Yang; Chang Quan Wang; Shun Qiang Zheng; Rui Xiao; Yong Guo (Environmental Science and Pollution Research, 2019)

Diagentic features of illite in Upper Triassic Chang-7 tight oil sandstones, Ordos Basin - Ai Wang; Dakang Zhong; Haihua Zhu; Lele Guo; Yangjinfeng Jiang; Xueqi Yang; Rui Xie (Geosciences Journal, 2019)

Cytoprotective Mechanism of the Novel Gastric Peptide BPC157 in Gastrointestinal Tract and Cultured Enteric Neurons and Glial Cells - Xi-Yu Wang; Meihua Qu; Rui Duan; Dengping Shi; Ling Jin; Jinping Gao; Jackie D. Wood; Junhua Li; Guo-Du Wang (Neuroscience Bulletin, 2019)

Comparative detection of Karenia mikimotoi by exponential rolling circle amplification (E-RCA) and double-ligation E-RCA - Chunyun Zhang; Rui Sun; Yuanyuan Wang; Guofu Chen; Changlu Guo; Jin Zhou (Journal of Applied Phycology, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Integrated drought risk assessment of multi-hazard-affected bodies based on copulas in the Taoerhe Basin, China - Rui Wang; Jiquan Zhang; Enliang Guo; Si Alu; Danjun Li; Si Ha; Zhenhua Dong (Theoretical and Applied Climatology, 2019)

Genome-Wide Identification of Circular RNAs in Fungal Parasite Nosema ceranae - Rui Guo; Dafu Chen; Huazhi Chen; Cuiling Xiong; Yanzhen Zheng; Chunsheng Hou; Yu Du; Sihai Geng; Haipeng Wang; Zhou Dingding; Guo Yilong (Current Microbiology, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Biglycan, a Nitric Oxide-Downregulated Proteoglycan, Prevents Nitric Oxide-Induced Neuronal Cell Apoptosis via Targeting Erk1/2 and p38 Signaling Pathways - Sujuan Chen; Dandan Guo; Wei Zhang; Yunfei Xie; Haijie Yang; Binfeng Cheng; Lei Wang; Rui Yang; Jiajia Bi; Zhiwei Feng (Journal of Molecular Neuroscience, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Effects of Fluoride on SOD and CAT in Testis and Epididymis of Mice - Zilong Sun; Sujuan Li; Zhenzhen Guo; Rui Li; Jixiang Wang; Ruiyan Niu; Jundong Wang (Biological Trace Element Research, 2018)

Modeling impacts of climate change on the geographic distribution of medicinal plant Fritillaria cirrhosa D. Don - Qi Zhao; Rui Li; Yingying Gao; Qian Yao; Xiaoqiang Guo; Wenguo Wang (Plant Biosystems, 2018)

Assessing non-linear variation of temperature and precipitation for different growth periods of maize and their impacts on phenology in the Midwest of Jilin Province, China - Enliang Guo; Jiquan Zhang; Yongfang Wang; Si Alu; Rui Wang; Danjun Li; Si Ha (Theoretical and Applied Climatology, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Potentiation effects by usnic acid in combination with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Rui-Chun Fu; Wei Yu; Yun-Ling Zhang; Gen-Chun Wang (Medicinal Chemistry Research, 2018)

A novel bispecific antibody fusion protein co-targeting EGFR and CD47 with enhanced therapeutic index - Yun Yang; Rui Guo; Qi Chen; Youxun Liu; Pengfei Zhang; Ziheng Zhang; Xi Chen; Tianyun Wang (Biotechnology Letters, 2018)

Alleviation of Arsenic-Induced Pulmonary Oxidative Damage by GSPE as Shown during In vivo and In vitro Experiments - Meng Wei; Fangming Guo; Dongsheng Rui; Haixia Wang; Gangling Feng; Shugang Li; Guanling Song (Biological Trace Element Research, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

Association between coal consumption and urbanization in a coal-based region: a multivariate path analysis - Xiaojia Guo; Zilong Zhang; Rui Zhao; Guokui Wang; Jing Xi (Environmental Science and Pollution Research, 2018)

Inhibitory effects of Dioscin on atherosclerosis and foam cell formation in hyperlipidemia rats - Ping Wang; Li-ya He; Guo-dong Shen; Rui-lin Li; Jun-li Yang (Inflammopharmacology, 2017)

Residents’ environmental conservation behaviour in the mountain tourism destinations in China: Case studies of Jiuzhaigou and Mount Qingcheng - Yu-ling Zhang; Jie Zhang; Hong-ou Zhang; Ruo-yang Zhang; Yang Wang; Yong-rui Guo; Zong-cai Wei (Journal of Mountain Science, 2017)

The N-terminal and central domain of colicin A enables phage lysin to lyse Escherichia coli extracellularly - Guangmou Yan; Jianfang Liu; Qiang Ma; Rining Zhu; Zhimin Guo; Chencheng Gao; Shuang Wang; Ling Yu; Jingmin Gu; Dongliang Hu; Wenyu Han; Rui Du; et al. (Antonie van Leeuwenhoek, 2017)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

A Carbazole-Fused-RhodamineProbe for Detection of HOCl in Living Cells - Rui Guo; Qiuan Wang; Weiying Lin (Journal of Fluorescence, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

A Ratiometric and near-Infrared Fluorescent Probe for Imaging Cu2+ in Living Cells and Animals - Rui Guo; Qiuan Wang; Weiying Lin (Journal of Fluorescence, 2017)

Evaluation of bioaugmentation and biostimulation on arsenic remediation in soil through biovolatilization - Peng Chen; Jin Li; Hong-Yan Wang; Rui-Lun Zheng; Guo-Xin Sun (Environmental Science and Pollution Research, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Insights into the Therapeutic Potential of Heparinized Collagen Scaffolds Loading Human Umbilical Cord Mesenchymal Stem Cells and Nerve Growth Factor for the Repair of Recurrent Laryngeal Nerve Injury - Yongqin Pan; Genlong Jiao; Jingge Yang; Rui Guo; Jinyi Li; Cunchuan Wang (Tissue Engineering and Regenerative Medicine, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Paleogene-Neogene stratigraphic realm and tectonic-sedimentary evolution of the Qilian Mountains and their surrounding areas - LiRong Yang; JianXing Li; LePing Yue; HongLiang Wang; HuaiJun Guo; XiaoHui Zhu; Tao Zhu; Kai Du; Rui Zhang; YunXiang Zhang; HuJun Gong (Science China Earth Sciences, 2017)

Warming Effects on Ecosystem Carbon Fluxes Are Modulated by Plant Functional Types - Ji Chen; Yiqi Luo; Jianyang Xia; Kevin R. Wilcox; Junji Cao; Xuhui Zhou; Lifen Jiang; Shuli Niu; Katerina Y. Estera; Rujin Huang; Feng Wu; Tafeng Hu; et al. (Ecosystems, 2017)

Physiological characteristics and metabolomics of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene under high temperature stress - Xueli Qi; Weigang Xu; Jianzhou Zhang; Rui Guo; Mingzhong Zhao; Lin Hu; Huiwei Wang; Haibin Dong; Yan Li (Protoplasma, 2017)

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)

Spatial distribution of soil cadmium and its influencing factors in peri-urban farmland: a case study in the Jingyang District, Sichuan, China - Bing Li; Rui Xiao; Changquan Wang; Linhai Cao; Yi Zhang; Shunqiang Zheng; Lan Yang; Yong Guo (Environmental Monitoring and Assessment, 2017)

Thermal state of soils in the active layer and underlain permafrost at the kilometer post 304 site along the China-Russia Crude Oil Pipeline - Yong-ping Wang; Guo-yu Li; Hui-jun Jin; Lan-zhi Lu; Rui-xia He; Peng Zhang (Journal of Mountain Science, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Inoculation of Fe/Mn-oxidizing bacteria enhances Fe/Mn plaque formation and reduces Cd and As accumulation in Rice Plant tissues - Ming Fang Dong; Ren Wei Feng; Rui Gang Wang; Yang Sun; Yong Zhen Ding; Ying Ming Xu; Zhi Lian Fan; Jun Kang Guo (Plant and Soil, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Submerged macrophytes shape the abundance and diversity of bacterial denitrifiers in bacterioplankton and epiphyton in the Shallow Fresh Lake Taihu, China - Zhou Fan; Rui-ming Han; Jie Ma; Guo-xiang Wang (Environmental Science and Pollution Research, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Antimicrobial activity of human β-defensins against lactic acid bacteria - Xiao-Fang Wang; Fei Tian; Rui-Ming Cao; Jing Li; Sheng-Mei Wu; Xiao-Kui Guo; Tong-Xin Chen (Natural Product Research, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Regulation of three isoforms of SOD gene by environmental stresses in citrus red mite, Panonychus citri - Ying-Cai Feng; Chong-Yu Liao; Wen-Kai Xia; Xuan-Zhao Jiang; Feng Shang; Guo-Rui Yuan; Jin-Jun Wang (Experimental and Applied Acarology, 2015)

Erratum to: Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Effects of alfalfa saponin extract on mRNA expression of Ldlr, LXRα, and FXR in BRL cells - Xin-ping Liang; Dong-qiang Zhang; Yan-yan Chen; Rui Guo; Jie Wang; Cheng-zhang Wang; Ying-hua Shi (Journal of Zhejiang University-SCIENCE B, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

PtAKT1 maintains selective absorption capacity for K+ over Na+ in halophyte Puccinellia tenuiflora under salt stress - Pei Wang; Qiang Guo; Qian Wang; Xiang-Rui Zhou; Suo-Min Wang (Acta Physiologiae Plantarum, 2015)

Solubilization of 4,4′-dibromodiphenyl ether under combined TX-100 and cosolvents - Xingjian Yang; Guining Lu; Rui Wang; Chuling Guo; Hongliang Zhang; Zhi Dang (Environmental Science and Pollution Research, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Assessing winter oilseed rape freeze injury based on Chinese HJ remote sensing data - Bao She; Jing-feng Huang; Rui-fang Guo; Hong-bin Wang; Jing Wang (Journal of Zhejiang University-SCIENCE B, 2015)

The Influence of Land Use on the Abundance and Diversity of Ammonia Oxidizers - Dayong Zhao; Juan Luo; Jianqun Wang; Rui Huang; Kun Guo; Yi Li; Qinglong L. Wu (Current Microbiology, 2015)

Zircon U–Pb geochronology and geochemistry of the Maoliger quartz monzodiorites, Inner Mongolia, China: implications for Carboniferous arc magmatism and closure of the Palaeo-Asian Ocean - Li-Min Wang; Xiao-Guo Chi; Zhi Zhao; Wei Sun; Rui Zhang; Shi-Yu Pan; Jing-Yu Quan (International Geology Review, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Irregular western margin of the Yangtze block as a cause of variation in tectonic activity along the Longmen Shan fault zone, eastern Tibet - Xiaoyu Guo; G. Randy Keller; Rui Gao; Xiao Xu; Haiyan Wang; Wenhui Li (International Geology Review, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

Identification of a novel fumarase C from Streptomyces lividans TK54 as a good candidate for l-malate production - Rui-Rui Su; Ao Wang; Song-Tao Hou; Peng Gao; Guo-Ping Zhu; Wen Wang (Molecular Biology Reports, 2014)

The apoptosis of peripheral blood lymphocytes promoted by hyperbaric oxygen treatment contributes to attenuate the severity of early stage acute pancreatitis in rats - Xuewei Bai; Zengfu Song; Yanmei Zhou; Shangha Pan; Feng Wang; Zuoming Guo; Maitao Jiang; Gang Wang; Rui Kong; Bei Sun (Apoptosis, 2014)

New isoflavones with cytotoxic activity from the rhizomes of Iris germanica L. - Guo-Yong Xie; Xiao-Ying Qin; Rui Liu; Qi Wang; Bin-Bin Lin; Guo-Kai Wang; Guang-Kai Xu; Rui Wen; Min-Jian Qin (Natural Product Research, 2013)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

A new species of Andricus oak gallwasp from China (Hymenoptera: Cynipidae: Cynipini) - Yiping Wang; Rui Guo; Xuexin Chen (Biologia, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Selection and characterization of colorectal cancer cell-specific peptides - Han Wang; Caixia Ma; Rui Li; Yonge Guo; Yakun He; Xiaojing Wang; Yiwen Chen; Yingchun Hou (Biotechnology Letters, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Novel association of a PROC variant with ischemic stroke in a Chinese Han population - Xuan Lu; Liang Tang; Kang Xu; Jie Ma; Tao Guo; Heng Mei; Rui Yang; Jianming Yu; Qingyun Wang; Yan Yang; Xiaorong Jian; Yu Hu (Human Genetics, 2013)

Molecular characterization of Chinese Hop stunt viroid isolates reveals a new phylogenetic group and possible cross transmission between grapevine and stone fruits - Zhixiang Zhang; Ying Zhou; Rui Guo; Lingxiao Mu; Yuanai Yang; Shifang Li; Hongqing Wang (European Journal of Plant Pathology, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Highly Selective and Sensitive Chemosensor for Hg2+ Based on the Naphthalimide Fluorophore - Rui Yang; Xiangfeng Guo; Wei Wang; Yu Zhang; Lihua Jia (Journal of Fluorescence, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Expression and Clinical Significance of CK19 and CK20 Expressions in Transverse Mesocolon Biopsies from Patients with Gastric Carcinoma - Guo-Rui Sun; Xiao-Yuan Dong; Qing-Si He; Hui Qu; Yan-Min Wang (Cell Biochemistry and Biophysics, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Purification and partial characterization of glutathione S-transferases from three field populations of Panonychus citri (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Bao-Jun Wang; Guo-Na Zhang; Rui Zhang; Yi Yin; Jin-Jun Wang (Experimental and Applied Acarology, 2012)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

Olig1 and ID4 interactions in living cells visualized by bimolecular fluorescence complementation technique - Shu-Jun Guo; Jian-Guo Hu; Bao-Ming Zhao; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü (Molecular Biology Reports, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Organochlorine pesticides in the soil of a karst cave in Guilin, China - Yinghui Wang; Songjun Guo; Rui Xue; Shihua Qi; Yiyin Xu; Baoming Xue; Daoxian Yuan (Environmental Monitoring and Assessment, 2011)

Effects of low nitrogen and drought stresses on proline synthesis of Jatropha curcas seedling - Wen-Guo Wang; Rui Li; Bin Liu; Liang Li; Sheng-Hua Wang; Fang Chen (Acta Physiologiae Plantarum, 2011)

Construction of the yeast whole-cell Rhizopus oryzae lipase biocatalyst with high activity - Mei-ling Chen; Qin Guo; Rui-zhi Wang; Juan Xu; Chen-wei Zhou; Hui Ruan; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

Experimental Validation of Retardation of Tritium Migration in the Chinese Loess Media - Rui Zuo; Yanguo Teng; Jinsheng Wang; Qinhong Hu; Minli Guo (Water, Air, & Soil Pollution, 2011)

A three-dimensional finite element model of the cervical spine: an investigation of whiplash injury - Jian-Guo Zhang; Fang Wang; Rui Zhou; Qiang Xue (Medical & Biological Engineering & Computing, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

The effect of the expression of angiotensin II on extracellular matrix metalloproteinase inducer (EMMPRIN) in macrophages is mediated via the AT1/COX-2/PGE2 pathway - Li-xia Yang; Jin-shan Ye; Rui-wei Guo; Hong Liu; Xian-mei Wang; Feng Qi; Chuanming Guo (Inflammation Research, 2010)

The functional expression of calcium-sensing receptors in BRL cells and related signal transduction pathway responsible for intracellular calcium elevation - Wenjing Xing; Guangwei Li; Yuhui Xi; Jin Guo; Hongzhu Li; Hongxia Li; Weihua Zhang; Li Zhang; Lingyun Wu; Rui Wang; Changqing Xu (Molecular and Cellular Biochemistry, 2010)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Seasonal variation analysis of atmospheric CH4, N2O and CO2 in Tianjin offshore area - ShaoFei Kong; Bing Lu; Bin Han; ZhiPeng Bai; Zhun Xu; Yan You; LiangMao Jin; XiaoYang Guo; Rui Wang (Science China Earth Sciences, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Research development of the pathogenesis pathways for neuroschistosomiasis - Peng Wang; Ming-Can Wu; Shi-Jie Chen; Guo-Cai Luo; Xiang-Ling Cheng; Zhan-Sheng Zhu; Guang-Rui Zhao (Neuroscience Bulletin, 2010)

A PKC-β inhibitor protects against cardiac microvascular ischemia reperfusion injury in diabetic rats - Liping Wei; Dongdong Sun; Zhiyong Yin; Yuan Yuan; Andrew Hwang; Yingmei Zhang; Rui Si; Rongqing Zhang; Wenyi Guo; Feng Cao; Haichang Wang (Apoptosis, 2010)

Genetic transformation of the bast fiber plant ramie (Boehmeria nivea Gaud.) via Agrobacterium tumefaciens - Xiongfeng Ma; Chunming Yu; Shouwei Tang; Sandui Guo; Rui Zhang; Yanzhou Wang; Aiguo Zhu; Siyuan Zhu; Heping Xiong (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Inhibitor of DNA binding-1 promotes the migration and proliferation of endothelial progenitor cells in vitro - Hong Wang; Yang Yu; Rui-wei Guo; Yan-kun Shi; Ming-bao Song; Jian-fei Chen; Shi-yong Yu; Yang-guang Yin; Pan Gao; Lan Huang (Molecular and Cellular Biochemistry, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Hydrochemical and isotopic evidence of origin of thermal karst water at Taiyuan, northern China - Teng Ma; Yanxin Wang; Qinghai Guo; Chunmiao Yan; Rui Ma; Zheng Huang (Journal of Earth Science, 2009)

Molecular characterization of a member of a new species of grapevine viroid - Dongmei Jiang; Rui Guo; Zujian Wu; Hongqing Wang; Shifang Li (Archives of Virology, 2009)

Activity of the Antimicrobial Peptide and Thanatin Analog S-thanatin on Clinical Isolates of Klebsiella pneumoniae Resistant to Conventional Antibiotics with Different Structures - Guo-Qiu Wu; Jia-Xuan Ding; Lin-Xian Li; Hai-liang Wang; Rui Zhao; Zi-Long Shen (Current Microbiology, 2009)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Molecular characterization of grapevine yellow speckle viroid-2 (GYSVd-2) - Dongmei Jiang; Zhixiang Zhang; Zujian Wu; Rui Guo; Hongqing Wang; Peige Fan; Shifang Li (Virus Genes, 2009)

Tumor-inhibitory and liver-protective effects of Phellinus igniarius extracellular polysaccharides - Wei Dong; Li Ning; Wei-dong Lu; Cui-cui Li; Rui-peng Chen; Xiao-ning Jia; Lin Wang; Li-zhong Guo (World Journal of Microbiology and Biotechnology, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Involvement of PDCD5 in the regulation of apoptosis in fibroblast-like synoviocytes of rheumatoid arthritis - Ning Wang; Hou-Shan Lu; Zhen-Peng Guan; Tie-Zheng Sun; Ying-Yu Chen; Guo-Rui Ruan; Zhan-Kun Chen; Jun Jiang; Chu-Jie Bai (Apoptosis, 2007)

Grifolin induces apoptosis via inhibition of PI3K/AKT signalling pathway in human osteosarcoma cells - Song Jin; Rui-Ping Pang; Jing-Nan Shen; Gang Huang; Jin Wang; Jia-Guo Zhou (Apoptosis, 2007)

An experimental study of the mechanisms of freeze/thaw and wind erosion of ancient adobe buildings in northwest China - Jian-Jun Qu; Guo-Dong Cheng; Ke-Cun Zhang; Jia-Cheng Wang; Rui-Ping Zu; Hai-Yan Fang (Bulletin of Engineering Geology and the Environment, 2007)

pEGFP-T, a novel T-vector for the direct, unidirectional cloning and analysis of PCR-amplified promoters - Baoli Wang; Xiaoxia Li; Fang Zheng; Rui Liu; Jinxing Quan; Hui Liang; Shanyi Guo; Gang Guo; Jingyu Zhang (Biotechnology Letters, 2007)

Changes of Bt Toxin in the Rhizosphere of Transgenic Bt Cotton and its Influence on Soil Functional Bacteria - Yu-Kui Rui; Guo-Xiang Yi; Jing Zhao; Bao-Min Wang; Zhao-Hu Li; Zhi-Xi Zhai; Zhong-Pei He; Qing X. Li (World Journal of Microbiology and Biotechnology, 2005)

Research progress of socio-economic water cycle in China - Jia Shao-feng; Wang Guo; Zhang Shi-feng; Yu Gui-rui; Wang Jin-xia; Xia Jun (Journal of Geographical Sciences, 2002)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)